Developing a Neuronal Differentiation Score for quantitative assessment of glutamatergic differentiation in human neuroblastoma cells - Lina Lin; Wenlong Yan; Enze Zhang; Wenjie Xu; Xiaokai Sui; Hui Zheng; Ting Xiao; Cheng Ni (Tissue and Cell, 2027)

De novo determination of fucose linkages in N-glycans using logically derived sequence tandem mass spectrometry - Jien-Lian Chen; Hsien-Wei Tseng; Chun-Cheng Lin; Chi-Kung Ni (Glycoconjugate Journal, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Repeated recharge of primitive melts in the lower oceanic crust: Constraints from the Dongco ophiolite, Central Tibet - Xiao-Ni Li; Chuan-Zhou Liu; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang (Lithos, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Trade-offs between microbial carbon use efficiency and nutrient use efficiency along an elevational gradient in arid mountain ecosystem - Shuhui Liu; Wenchang Ma; Lin Chen; Xilu Ni; Guangyao Shi; Yang Hu; Xuebin Li; Jinxing Zhou; Danbo Pang; Mengyao Wu; Akash Tariq (CATENA, 2026)

Coupling between microbial nutrient limitation and soil microbial community assembly in an arid mountain ecosystem - Wenchang Ma; Shuhui Liu; Lin Chen; Guangyao Shi; Yang Hu; Xilu Ni; Xuebin Li; Jinxing Zhou; Danbo Pang; Mengyao Wu; Geshere Abdisa Gurmesa (Applied Soil Ecology, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

BlOFP1 is associated with reduced secondary cell wall formation and interacts with BlKNOX9 and BlBLH9 in Betula luminifera - Fei Ni; Xian-Ge Hu; Hebi Zhuang; Fuqiang Cui; Yousry A. El-Kassaby; Erpei Lin; Huahong Huang (Plant Science, 2026)

Sequence-optimized acetylacetone-chitosan cascade process for cyanobacterial control: Treatment performance, microcystin release, and floc-accumulation risk - Li Yin; Lin Xu; Kaipian Shi; Yong Zhang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Water Process Engineering, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Research on the regulation mechanism of CaO on NO formation during the co-combustion of sewage sludge and wheat straw - Zhanshi Ni; Qizhao Lin; Kesheng Meng; Chunlong Jiang; Haobo Bi (Journal of Environmental Chemical Engineering, 2026)

The accumulation and regulation mechanisms of microbial residual carbon along an elevation gradient in dryland mountains - Danbo Pang; Lin Chen; Ansa Rebi; Hui Li; Guangyao Shi; Yang Hu; Jinxing Zhou; Xilu Ni; Xuebin Li; Mengyao Wu; Geshere Abdisa Gurmesa (Fungal Ecology, 2026)

Multi-omics analysis provides mechanistic insights into tanninase-assisted flavor evolution in Phyllanthus emblica L. wine - Jie Chen; Xinyong Zhang; Ni Liu; Xujie Chen; Yue Wang; Qi Lin; Yuanyuan Bao (Food Chemistry, 2026)

Sulfobutylether-(hydroxypropyl-β-cyclodextrin) bonded silica as stationary phase for enhancing chiral separation in liquid chromatography - Linna Xu; Ankang Li; Jialong Wang; Gaosheng Yang; Liqin Lin; Keer Yu; Huizhen Ni; Wentao Xu; Junchao Zhu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2026)

Soil development constrains N availability through regulating N cycling in subtropical karst regions - Guan Wang; Lin Yang; Kang Ni; Jinxing Zhou; Zeyan Wu; Tongbin Zhu; Christoph Müller (Journal of Environmental Management, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Whole-genome sequencing and metagenomic analyses provide genomic insights into tannin and saponin degradation regulated by lactic acid bacteria in anaerobic fermentation of paper mulberry - Ningwei Wang; Yunlei Sun; Yiying Shen; Mingxin Wu; Yanli Lin; Xuekai Wang; Kuikui Ni; Fuyu Yang (Food Bioscience, 2026)

Betanodavirus induces RIPK3/MLKL-mediated necroptosis and IL-21/adaptive immune response via superoxide stress/mTOR/ULK1-mediated autophagy signal in the context of brain damage in grouper (Epinephelus coioides) - Hong-Jun Liao; Kuang-Wen Chen; Hsing-Ni Lin; Pei-Cih Gong; Jen-Leih Wu; Jiann-Ruey Hong (Fish & Shellfish Immunology, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Highly charged nanocellulose enables triple-function hydrogels for bionic electronic skins - Danning Fu; Jiawen Wu; Huiming Xiao; Yonghao Ni; Zhixin Jia; Wanqing Wang; Lin Li (Chemical Engineering Journal, 2026)

Photo-induced Agδ+-Agδ− relay on flexible Cu-MOF enables bidirectional charge transfer for enhanced photocatalytic H2O2 synthesis - Shao-Chuan Li; Huanhuan Li; Shui-Sheng Chen; Xiao-Ni Zheng; Lijun Liu; Yuan Lin (Chemical Engineering Journal, 2026)

Charged cellulose-inserted-nonwoven fabric composite membrane for selective Mg2+/Li+ separation - Yingchao Wang; Zhen Wang; Qiyang Lu; Qingxian Miao; Yonghao Ni; Liulian Huang; Lihui Chen; Zhiwei Lin; Yuxin Liu; Jianguo Li (Chemical Engineering Journal, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

NCSSD-YOLO: a non-causal state space duality-based instance segmentation model for pacific white shrimp - Weiqiang Ni; Chenqing Zhang; Yiqing Zhang; Siyi Li; Haitao Wang; Chenchen Wu; Lin Luo; Qinglang Liang; Zequn Peng; Shenghua Li; Yanqing Chen; Shiyin Chen; et al. (Aquaculture International, 2026)

From radical/electron competition to interfacial shielding: How PFOA and its derivatives obstruct electrochemical degradation of microplastics - Yuehua Zhang; Shengping Yang; Yinghui Lin; Xianfang Fan; Mengjuan Yao; Shihua Yin; Yuanji Shi; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2026)

Stepwise enhanced photoelectrochemical activity of BiOCl by Fe(III)-doping and aptamer immobilization for ultrasensitive detection of tetracycline - Yifan Chen; Yuan Zhu; Yiyang Lin; Feng Gao; Zhiping Song; Xiaohui Dai; Jiancong Ni; Qingxiang Wang (Food Chemistry, 2026)

Profiles and maternal-to-fetal transfer of per- and polyfluoroalkyl substances in paired maternal-infant biological matrices: A birth cohort study in Chengdu, China - Jing Zhang; Mengmei Ni; Liang Wang; Lin Ren; Yeqiu Miao; Lishi Zhang; Li Yong; Jinyao Chen (Environmental Research, 2026)

Di(2-ethylhexyl) phthalate (DEHP)-induced circadian disruption accelerates aging-related functional declines via oxidative stress and insulin/IGF-1 signaling in Caenorhabditis elegans - Pei-Ling Yen; Wei Lin Chuah; Sin Ni; Tzu-Ting Chang; Mu-En Huang; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Chronic intermittent hypoxia sustains the low-grade inflammatory memory of monocytes via activation of myelopoiesis - Shi Qi Li; Yi Wang; Meng Yao Li; Liu Zhang; Xi Xi Chen; Ying Ni Lin; Li Na Zhou; Xian Wen Sun; Yong Jie Ding; Qing Yun Li (Inflammation Research, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

Structuring urban carbon metabolism through cross-sectoral and cross-media linkages: Evidence from a high-density city - Yu Lin; Jiahao Shi; Yichen Dong; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Sustainable Cities and Society, 2026)

Hemodynamic decoding for multimodal connected cardiovascular healthcare - Yun Ke; Ruijun Pan; Jun Li; Wanghuai Xu; Dalong Ni; Zhou Li; Zhong Lin Wang; Fan Yang (Science Bulletin, 2026)

Multidrug-resistant bacteria contribute to core bacterial community and ARGs persistence during full-scale pharmaceutical wastewater treatment - Xiaojie Sun; Zhiquan Lin; Shou-Qing Ni (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Life cycle assessment of regionally functionally-zoned intensive pig farming systems: Carbon footprint analysis and mitigation strategies for sustainable production - Bing Wu; Zhiqi Wen; Zhepu Ruan; Xiaoxuan Lin; Yongjie Li; Zhuobiao Ni; Gengyuan Cai; Rongliang Qiu (Journal of Environmental Management, 2026)

Dynamic thermal comfort in part-time-local-space heating mode: Interplay effects of localized space heating terminal forms and zonal temperature transitions - Mengfan Duan; Minghao Sun; Shenfei Yu; Hongli Sun; Shenyang Ni; Yifan Wu; Borong Lin; Dongliang Zhao (Energy and Buildings, 2026)

High-Efficiency N-acetylneuraminic acid biosynthesis in plasmid-free Escherichia coli MG1655 - Qian Lin; Yuanlin Liu; Wenbo Zhang; Liping Qiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

Spontaneous plastome mutations in variegated plants occur predominantly in genes related to transcription and photosynthesis - Zhuoqiao Qiu; Boya Yi; Huajing Feng; Qi Zeng; Peishan Zou; Xirong Zheng; Jianzhong Ni; Manmei He; Ruiying Wang; Shuaixi Zhou; Kainan Ma; Shiou Yih Lee; et al. (Planta, 2026)

Application of a next generation risk assessment framework, integrated testing strategy defined approaches and read-across for evaluating the skin sensitization potency: Case studies with 5-hydroxymethylfurfural and 5,5′-oxydimethylenebis (2-furfural) - Ni Lin; Jianing Zhang; Ying Liu; Fenglan Zhang; Gangli Wang; Zhenxi Yu; Hongtao Jin; Yong Lu (Regulatory Toxicology and Pharmacology, 2026)

Analytical study of Bragg reflection by an array of rectified cosinoidal bars or trenches on a fringing reef flat - Jian-Jian Xie; Ming-Xuan Zhu; Yun-Lin Ni; Jinbao Wang (Ocean Engineering, 2026)

Degradation of paralytic shellfish toxins and inactivation of Gymnodinium catenatum using potassium monopersulfate-based advanced oxidation processes - Zhang Kang; Zhuoru Lin; Rui Ni; Mingbao Feng; Guangmao Ding; YiWen Huang; Kefu Zhou (Journal of Environmental Chemical Engineering, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Carbon-fiber-grid heated pavement for deicing and snow melting: The role of design parameters and environmental conditions - Xinxing Bian; Huining Xu; Lin Chen; Lin Zhang; Jianhong Ni; Yong Lai (Cold Regions Science and Technology, 2026)

Precipitation reduction mitigates the negative impact of nitrogen deposition on soil nitrogen fixation in subtropical Chinese fir plantations - Fengyi Han; Yongxin Lin; Maokui Lyu; Hang-Wei Hu; Xiangyin Ni; Qiufang Zhang; Jinsheng Xie; Ji-Zheng He; Peter M. Homyak (Science China Life Sciences, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Nighttime apple harvesting image enhancement based on a global–local feature fusion diffusion model - Liuchang Xu; Ting Ni; Fangshuo Zhou; Qingming Lin; Luyao Chen; Qianqian Luo; Kai Xia; Xingyu Xue; Xinyu Zheng; Sensen Wu; Zhenhong Du; Kai Fang; et al. (Computers and Electronics in Agriculture, 2026)

Biodegradation of tetracycline antibiotics: Advances and insights into microbial resources, enzymatic mechanisms, and remediation potential - Aojie Lei; Mengyao Wang; Yaxin Pei; Qipeng Cheng; Hongyuhang Ni; Sen Yang; Hui Lin; Xinyu Liu; Hongge Chen (Journal of Hazardous Materials, 2026)

Modulating molecular assembly behavior of myosin under freeze-thaw treatment using EGCG for improving gel and physicochemical properties at low ionic strength - Xi Zhou; Zhichao Xiao; Yatong Wang; Jianmei Zheng; Laixue Ni; Xianqi Yao; Lin Chen; Xianchao Feng; Yabin Niu (Food Research International, 2026)

Harnessing dual-stable conformers in o-carborane-based multi-resonance emitters for achieving single-emitter white OLEDs - Zezhu Xiao; Chen-Yu Lin; Jianxing Chen; Songqian Ni; Xingtian Wang; Ming-Yu Teng; Weiguo Zhu; Pi-Tai Chou; Xiugang Wu (Chemical Engineering Journal, 2026)

Mutations in PilZ domains of newly discovered bacterial β-(1,3;1,4)-mixed linkage glucan synthases modulate polysaccharide production - Rebecka Karmakar Saldivar; Shu-Chieh Susie Chang; Sheileza Rajkumari; Rico A. Pratama; Yen-Ting Lin; Mu-Rong Kao; Christina Divne; Chi-Kung Ni; Yves S.Y. Hsieh (Carbohydrate Polymers, 2026)

Unannotated noncoding transcripts as a source of intratumor heterogeneity in malignant cell states - Xiaolan Zhou; Limin Lin; Yu Chen; Guangrui Yang; Ting Ni; Zhaozhao Zhao (Science China Life Sciences, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Susceptibility to eight common chemical insecticides in Helicoverpa zea populations from the southern United States - Bhavana Patla; Tiago Silva; Shucong Lin; Graham P. Head; Francis P.F. Reay-Jones; Xinzhi Ni; Lina Bernaola; Sebe Brown; Don Cook; James Villegas; Jeffrey A. Davis; Fangneng Huang (Crop Protection, 2026)

Sources, flux, and potential risks of heavy metals in soils around the smelting and mining area - Luyao Jin; Yonghui Ni; Xiaoli Liu; Zhaofeng Li; Xiaoyan Xu; Qingzhu Li; Zhihui Yang; Lin Luo; Xiande Xie (Journal of Environmental Sciences, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Enhanced antibacterial activity against multidrug-resistant Mycobacterium tuberculosis of nano‑silver prepared by Konjac glucomannan via asymmetric flow field-flow fractionation - Wenying Wang; Jing Liu; Chao Hong; Ni Zhang; Lin Lin; Wenjie Jian (Carbohydrate Polymers, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Tree species dramatically reshape the functional traits of Collembola community in a subtropical forest common garden - Lindan Zheng; Huihui Wen; Xiaohao Lin; Jingjing Li; Jingni Wang; Kai Yue; Xiangyin Ni; Fuzhong Wu (Soil Ecology Letters, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Physiological Performance of Anadromous Masu Salmon (Oncorhynchus masou) in Relation to Salinity - Shihan Sun; Yuening Guo; Derun Yuan; Jiarun Lin; Huizhu Ni; Xuwang Yin (Fishes, 2026)
Salinity is a key environmental survival factor for all aquatic organisms, especially migratory species. The masu salmon (Oncorhynchus masou) is a representative migratory fish species. Following the freshwater parr stage, anadromous masu salmon briefly inhabit brackish water and transition before migrating to the ocean. To demonstrate the physiological responses of masu salmon (length: 8 ± 0.5 cm, water temperature: 10 ± 0.5 °C) to variations in salinity, we carried out three gradual transfer experiments (gradual daily increases direct transfer experiment of 3.2 (D10), 1.6 (D20), and 1.1 (D30) ppt until reaching 32 ppt) and one (immediate transfer to 32 ppt on day 0) as domestication regimens for masu salmon. The results indicated the following: (1) In the gradual transfer experiment group, growth performance, along with ion and hormone indicators, suggested that the D30 treatment group of anadromous masu salmon exhibited a high level of adaptability. (2) In the direct transfer experiment, in addition to the activity of antioxidant enzymes, both ion concentrations and hormone indicators returned to a stable state within 7 days. Our findings provide a scientific protocol for salinity regulation during the artificial propagation of masu salmon and establish critical acclimation parameters for land-based recirculating aquaculture systems aimed at marine salmonid farming, thereby highlighting their practical value.

Dynamic cross-sector and media assessment of urban phosphorus metabolism: underlying mechanisms, environmental implications, and driving forces - Yichen Dong; Yu Lin; Qingbin Song; Ni Sheng; Chen Chen; Zongguo Wen (Environment, Development and Sustainability, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Precipitation dominates remote lake primary productivity: A Holocene perspective based on regional synthesis from northeastern Asia - Dongliang Ning; Xianqiang Meng; Qi Lin; Enfeng Liu; Zhenyu Ni; Weiwei Sun; Wenfang Zhang; Yao Wang; Rong Chen; Enlou Zhang (Quaternary Science Reviews, 2026)

Underwater topography regulates the relationship between water depth and sedimentary n-alkane distributions in lakes - Durui Lin; Enlou Zhang; Weiwei Sun; Xianqiang Meng; Zhenyu Ni; Yao Wang (Quaternary Science Reviews, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Morphology and electronic configuration engineering of CoP as an excellent electrocatalyst for oxygen evolution reaction - Zhao Li; Wenjing Cheng; Chunmei Ni; Xuena Gao; Jianguo Dong; Huiming Yang; Wenyi Tan; Lin Tian (Fuel, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

From farm to table: The statuses, hotspots, and trends on research of HACCP application in global food supply chains (1990–2025)—A bibliometric analysis based on CiteSpace - Jiuhao Chen; Junfei Chen; Yuze Guan; Shijie Xue; Yinqiang Liu; Yifan Guo; Shisheng Zhu; Shiyu Quan; Tianci Lin; Zhihao Ni (Food Control, 2026)

Simplified analytical method for bell-spigot jointed pipeline response to normal faults using two-layer Winkler foundation model - Yuanlong Chen; Jianfeng Li; Qingshu Chen; Cungang Lin; Pengpeng Ni; Zhiwang Lu (Tunnelling and Underground Space Technology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Lake expansion enhances inorganic and organic carbon sinks in sediments of lake Qinghai, Tibetan Plateau - Xianqiang Meng; Han Zhou; Qi Lin; Xianming Zhang; Li Huo; Jiayi Li; Lingkai Meng; Zhenyu Ni; Enlou Zhang (Journal of Environmental Management, 2026)

Impact of infant feeding conditions on the survival and post-digestive regrowth of commercial probiotics in an in vitro gastrointestinal model - Juan Wang; Ni Wang; He Lyu; Peng Wu; Jia Lin; Xiao Dong Chen (International Dairy Journal, 2026)

Dual-phase engineered hierarchical CoP enables dynamic reconstruction and multimetallic synergy for superior oxygen evolution - Chunmei Ni; Xuena Gao; Huimin Yang; Jianguo Dong; Ju Wang; Changchun He; Zhao Li; Hui Xu; Lin Tian (Fuel, 2026)

Synthesis mechanism of antifungal active protein in the fermentation of agar waste liquid by Streptomyces rubiginosoheloolus - Xiping Du; Qiaoyan Lin; Yonghong Qin; Zhipeng Li; Yuanfan Yang; Zedong Jiang; Hui Ni; Qingbiao Li (Food Chemistry, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Reduction mediated iodide antioxidation: “Chemical Preservation” of precursor solution facilitates construction of high efficiency and stable wide bandgap inverted perovskite solar cells - Chao Liu; Yingchen Li; Hongkun Cai; Boyan Li; Shuping Lin; Qi Sun; Dalong Zhong; Jifeng Liu; Qinwen Guo; Zhiwen Xu; Juan Li; Jian Ni; et al. (Chemical Engineering Journal, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Seasonal dynamics of gut microbiota in rhesus macaques (Macaca mulatta) from western Sichuan Plateau and their adaptability to high altitude climate change - Fazal Karim; Qianqi Lin; Huan Xie; Shahla Nargis; Hongtao Xiao; Shengzhi Yang; Ying Xiong; Meng Xie; Qingyong Ni; Yongfang Yao; Huailiang Xu (Current Microbiology, 2026)

Mussel Production in the Global Blue Food System: Current Status, Sustainability Challenges, and Future Trajectories - Fan Li; Hai-Jie Gao; Yun-Lin Ni; Peng-Zhi Qi (Fishes, 2026)
This review examines the status, challenges, and future trajectories of global mussel aquaculture within the blue food system. Despite steady production growth, mussels’ relative contribution to total bivalve output has significantly declined over recent decades due to disproportionate expansion of oyster, clam, and scallop sectors. A major geographical production shift has occurred, with Asia, spearheaded by China, emerging as the dominant region, supplanting traditional European producers while the Americas rapidly ascend. China’s overwhelming dominance in overall bivalve production starkly contrasts with its underdeveloped mussel sector, where growth lags behind other bivalves despite substantial absolute increases, reflecting a fundamental restructuring of species composition. The industry faces interconnected sustainability constraints: persistent vulnerabilities in spat supply stemming from environmental variability, hatchery limitations, and disease transmission risks; escalating environmental stressors including climate change impacts, harmful algal blooms, pollution, and pathogens; structural flaws in value chains characterized by fragmented production, market volatility, and underutilized byproducts; and governance challenges related to spatial access and licensing inefficiencies. This review advocates for a comprehensive strategy to boost the mussel aquaculture. These encompass advancing hatchery technology and genetic breeding programs, implementing ecosystem-based management such as multi-trophic systems and AI-enhanced environmental monitoring, restructuring value chains through producer cooperation and high value product diversification, and establishing science-based spatial planning frameworks with streamlined governance. Addressing these challenges holistically is critical to position mussel farming as a resilient pillar of sustainable blue food production capable of reconciling ecological integrity with economic viability and social equity.

Post-cyclic undrained behaviour of marine soft clay under cyclic loading with variable confining pressure - Junhao Tong; Dongyang Yuan; Changjun Li; Haozheng Wang; Dingyu Ni; Ke Wu; Pixian Si; Qiang Wang; Lin Guo (Marine Georesources & Geotechnology, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Improving the utilization of summer tea leaves through steam explosion technology: flavor transformation and cold-brewing feasibility - Daoliang Wang; Zhibin Liu; Weiying Su; Yuan Lu; Xiaoxiao Feng; Yuan Liu; Jinsu Lin; Bo Wen; Meijuan Xiao; Li Ni (Food Chemistry, 2026)

Investigation on the heating performance of an ultra-low temperature air source heat pump system - Chongchong Hou; Chong Han; Hui Yan; Musen Lin; Long Ni (Energy and Buildings, 2026)

Closing the phosphorus loop: Turning aquaculture wastewater into slow-release fertilizer with an amine-modified wood fiber - Ni Yang; Lisha Wang; Yahui Ji; Yuanyuan Feng; Bingyu Wang; Lin Shi; Lihong Xue; Shiying He; Chen Ling; Yanfang Feng; Baoshan Xing (Chemical Engineering Journal, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Lipid–sugar conversion regulates early white clover (Trifolium repens) seedling establishment under cadmium stress - Yuting Wu; Long Lin; Wanlin Ni; Yankang Zhang; Qinghuang Li; Zhou Li (Planta, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Widespread weakening of soil-atmosphere thermal coupling and its response to climate warming on the Qinghai-Tibetan plateau - Guoan Yin; Xin Ju; Fujun Niu; Zhanju Lin; Jing Luo; Zeyong Gao; Hongye Yan; Yanhe Wang; Weiheng Ni (Agricultural and Forest Meteorology, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Intra-oceanic arc subduction within the Meso-Tethys Ocean constrained by arc crust remnants in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Xiao-Ni Li; Chang Zhang; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Time-varying strength characteristics of synchronous grouting materials derived from geopolymer-modified shield muck - Shuying Wang; Hui Zeng; Xiangsheng Chen; Xiangcou Zheng; Cong Zhang; Zhun-lin Ni (Journal of Cleaner Production, 2025)

Performance study of automotive heat pump system with different refrigerants and leakage combustion characteristics of R290 - Kang Li; Lin Wu; Soheil Mohtaram; Yafen Tian; Ni Liu; Hua Zhang; Jinjun Yan; Qize He; Chao Li; Tao Yang (International Journal of Refrigeration, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Streptococcal pyrogenic exotoxin a induces regulatory T cells via TNF-α-TNFR2 signaling - Chun-Hao Lu; Jason Ma; Ming-Chieh Lin; Cheng-Jang Wu; Chieh-Ying Kuo; Chuan Chiang-Ni; Ming-Ling Kuo (Medical Microbiology and Immunology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Integrative analysis identifies FERMT3 as a key regulator of metabolic reprogramming in keloid scarring and metabolic syndrome - Qian Lin; Beichen Cai; Feng Dong; Ruonan Ke; Xiuying Shan; Xuejun Ni; Lu Chen; Chuanshu Cai; Biao Wang (Functional & Integrative Genomics, 2025)

Spatio-temporal heterogeneity of the estuarine turbidity maximum retreat in the Changjiang river estuary under reduced sediment supply - Jie Feng; Qian Yu; Shiyi Cao; Shiyu Zhang; Tianxu Ni; Zhiyun Du; Hangjie Lin; Yunwei Wang; Ya Ping Wang (Geo-Marine Letters, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Maternal Genetic Diversity Analysis of Guanling Cattle by Mitochondrial Genome Sequencing - Longxin Xu; Xin Wang; Hua Wang; Junda Wu; Wenzhang Zhou; Mengmeng Ni; Kaikai Zhang; Yuanfeng Zhao; Ruiyi Lin (Biochemical Genetics, 2025)

High acyl gellan oligosaccharides trigger jasmonic acid-mediated immunity in Arabidopsis thaliana: Structural characterization and defense activation - Shousen Guo; Chen Zhao; Haifeng Ni; Kunlun Li; Song Zhang; Le Su; Qiulin Yue; Lin Zhao (Physiological and Molecular Plant Pathology, 2025)

Stability of RL-modified n-FeS and its mechanisms for Cr(VI) removal efficiency - Kaipian Shi; Junfeng An; Lin Xu; Li Yin; Chunqing Peng; Yong Zhang; Shiyin Li; Lixiao Ni (Journal of Water Process Engineering, 2025)

Surface-modified nanoplastics facilitate the dissemination and persistence of antibiotic resistance genes - Xiaojie Sun; Xue Chen; Jie Ming; Zhiquan Lin; Yue-Zhong Li; Bing-Jie Ni; Shou-Qing Ni (Journal of Hazardous Materials, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Co-encapsulation of an AKT Inhibitor Enhances the Tumor-cell Selectivity of STING Agonists in Co-delivery Liposomes - Ziyu Ge; Qiang Zhang; Yuming Wang; Lin Miao; Xinqi Wang; Ni Fan; LiLi Duan; Yunfei Li; Xue-Jie Qi (Pharmaceutical Research, 2025)

BDE-47 induces oxidative stress and apoptosis by interfering with pyruvate and glutathione metabolism in Epinephelus coioides - Zongfu Chen; Lei Yan; Peng Luo; Ziyang Xu; Tongwen Ni; Li Lin; Wei Zhang; Yanan Li (Aquaculture International, 2025)

Root architectural diversity underpins soil stabilisation in alpine grasslands: Trait-mediated mechanisms across rhizomatic, densely tufted, and sparsely tufted herbs - Junmei Gao; Lingshan Ni; Kexin Li; Ni Zhu; Lin Liu; Suyuan Jia; Laiting Zhang; Shixiong Li; Bing Liu; Xiaoli Wang; Yu Liu (Plant and Soil, 2025)

Estimating the vegetable yield and carbon reduction benefits of urban agriculture in Fuzhou based on planting intensity - Qunyue Liu; Zhiqian Lin; Taoyu Chen; Ni Zhang; Zubin Ye; Yourui Guo; Yaling Gao; Yuanping Shen; Weicong Fu; Yuanjing Wu (Sustainable Cities and Society, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Pilot-scale tests on struvite recovery from agricultural wastewater: the effects of seeding, growth kinetics, and crystallization mechanisms - Ruizhu Hu; Xingchen Liu; Ziqi Lin; Tinglin Huang; Gang Wen; ShouQing Ni (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Lateral Cerebellar Theta Burst Stimulation Can Modulate Default Mode Network Connectivity in Autistic Adults - Hsing-Chang Ni; Heng Chien; Chun-Hung Yeh; Michael Cheng; Wei-Cheng Lin; Hsiang-Yuan Lin (The Cerebellum, 2025)

Hippocampal subfield-specific alterations in post-stroke dementia with subcortical lesion - Guojun Xu; Bin Lin; Yun Jiang; Jie Ming; Linhui Ni; Guocan Han; Zhiyong Zhao; Huaying Cai; Lulu Gao (Brain Imaging and Behavior, 2025)

Optimizing co-combustion of sewage sludge and bamboo scraps: Analysis of NO emissions and ash slagging behavior - Xiang Liu; Zhanshi Ni; Junjian Tian; Kesheng Meng; Qizhao Lin (Waste Management, 2025)

Global marine methane seepage: Spatiotemporal patterns and ocean current control - Xin Ni; Xiuguo Liu; Shilong Pang; Yifei Dong; Binbin Guo; Yuhang Zhang; Yang Wu; Danyi Su; Andi Xu; Qingmeng Yuan; Xuemin Wu; Lin Yang; et al. (Marine Geology, 2025)

Mobilization of water-dispersible colloidal chromium and nickel in basalt-derived paddy soils: Role of Fe (hydr)oxides and organic matter - Ting Liu; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Exploring the iodine adsorption and deposition behavior: An out-of-pile experiment on accident conditions of lead-bismuth fast reactor - Chenyu Liu; Hanyu Wu; Yuqing Wang; Lili Li; Jiang Zhou; Jiewei Wu; Peng Lin; Muyi Ni (Journal of Hazardous Materials, 2025)

Constructing Ni2P/CoP heterojunction with stable built-in electric field to boost overall water splitting at industrial current density - Tian Lin; Huimin Yang; Jianguo Dong; Chunmei Ni; Xuena Gao; Jing Li; Ju Wang; Xiaoyan He; Wenyi Tan; Ligang Feng; Zhao Li (Fuel, 2025)

Influence of N2 and CO2 dilution on methane MILD combustion: Insights into temperature distribution and emission optimization - Junjian Tian; Yue Ma; Weiwei Song; Zhanshi Ni; Xiang Liu; Peng Hu; Kesheng Meng; Qizhao Lin (Fuel, 2025)

Multiple endogenous aldehydes amplify acetaminophen-induced liver injury - Hong Pan; Qi Luo; Qiuyi Jing; Lin Chen; Ni Li; Chao Fang; Fuguo Shi (Chemico-Biological Interactions, 2025)

Evaluation and Dissection of Sensory Quality Traits for Potato Taste - Ying Wang; Wan-lin Yang; Fan-kui Zeng; Chun-ni Lei; Qiong-fen Yang; Jian Wang (Potato Research, 2025)
The sensory qualities of potatoes significantly influence consumer preference. This study evaluated the sensory qualities of 66 potato varieties, focusing on representatives of distinct taste types for detailed analysis: sensory evaluation, taste, nutritional components, texture properties, physicochemical characteristics of starch, and volatile aroma compounds. Sensory evaluation of these potato varieties identified the landrace “Kaihua Yangyu” as the most favoured by consumers. The favourable taste of Kai Hua Yang Yu was attributed to (1) soft, dry, and non-sticky texture; (2) starch with higher peak viscosity, easier gelatinisation (below 70 ℃), higher setback value (2776 RVU), and larger granule size (41.63 ± 9.90 μm) compared with other such as YS105 and Cooperation88; and (3) distinctive umami flavour, a trait notably associated with elevated levels of aspartic acid and glutamic acid.

PFAS removal from reverse osmosis and nanofiltration brine by granular activated carbon: Thermodynamic insights into salinity effects - Jiefei Cao; Siyuan Feng; Alireza Arhami Dolatabad; Yue Zhi; Baolin Deng; Caihong Liu; Xueyan Lyu; Charlotte S.Q. Christensen; Joseph J. Pignatello; Pan Ni; Shihong Lin; Zongsu Wei; et al. (Water Research, 2025)

A review of umami taste of Tea: Substances, perception mechanism, and physiological measurement prospects - Yashu Yu; Xiaoxiao Feng; Imre Blank; Haoli Wang; Yiwen Zhu; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Trends in Food Science & Technology, 2025)

A hybrid biomanipulation strategy to regulate seasonal dynamics of phytoplankton in a subtropical mesocosm experiment - Feng Wang; Wenyi Dong; Hongjie Wang; Xiaohui Sun; Helong Song; Zijun Dong; Zhiqiang Zuo; Botao Ni; Yanbing Ni; Chen Lin; Yiping Rong; Xi Lin (Science of The Total Environment, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Microbiome dynamics and metabolic regulation in rumen fibre degradation: Insights into lignocellulose breakdown and rumen fermentation strategies - Xin Wang; Yufan Lin; Ruhui Wang; Mengyao Sun; Yuan Wang; Yanli Lin; Fuyu Yang; Kuikui Ni (Chemical Engineering Journal, 2025)

Narrowband deep-blue polymer light-emitting diodes: Beneficial from the individual planar-conformational chain segment in hierarchically ordered nano-domain - Bin Liu; Jiangli Cai; Yingying Zheng; Yang Xu; Jinghao Yang; Wenyu Chen; Mengyuan Li; Ningning Yu; Mingjian Ni; Lubing Bai; Chongping Song; Lili Sun; et al. (Chemical Engineering Journal, 2025)

First report of Botryosphaeria dothidea causing leaf blight on Yulania denudata in China - Lin Rui; Qiao-Qiao Zhang; Wei-Liang Kong; Hang Ni; Xiao-Qin Wu (Crop Protection, 2025)

Neighborhood Energy Supply-Demand Coordinated Design (NES-CoD) in early design stage - Junkang Song; Shuangdui Wu; Zihan Zhang; Hanjie Zheng; Pingan Ni; Shenfei Yu; Songjun Li; Hongli Sun; Borong Lin (Sustainable Cities and Society, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Effects of dietary Inonotus obliquus fermentation products supplementation on meat quality and antioxidant capacity of finishing pigs - Xiangyuan Li; Lin Zhang; Yimin Zhang; Xin Luo; Jiang Yu; Sufang Ren; Laixue Ni; Xianqi Yao; Jiaqiang Wu; Yanwei Mao (Meat Science, 2025)

Neurotoxic effects of per- and polyfluoroalkyl substances (PFAS) mixture exposure in mice: Accumulations in brain and associated changes of behaviors, metabolome, and transcriptome - Qiurong He; Qingkun Yang; Lin Wu; Yuhang He; Ni Zeng; Zhenglu Wang (Journal of Hazardous Materials, 2025)

Element mobilization characteristics and environmental impact of flowback water during fracturing fluid-shale interaction at different time scales - Qipan Liu; Yue Ni; Yong Lei; Huanhuan Zhao; Yashi Liu; Lin Gan; Zepeng Sun (Journal of Environmental Chemical Engineering, 2025)

Public dose assessment for Yangjiang nuclear power plant effluents: A multi-media numerical model of tritium transport in the South China sea - Junyang Zeng; Lili Li; Yingzhe Du; Ziliang Hou; Youting Wu; Shiying Li; Hanyu Wu; Zhihao Liu; Peng Lin; Muyi Ni; Xiajie Liu (Journal of Environmental Radioactivity, 2025)

Ultrahigh-efficiency and synchronous removal of microplastics-tetracycline composite pollutants via S-scheme core-shell magnetic nanosphere - Yujie Zhou; Xiaofeng Lin; Xin You; Ni Xue; Zilong Liu; Yanpeng Cai (Environmental Pollution, 2025)

Mantle evolution beneath a back-arc basin: Highly siderophile elements and Os isotope of Dongco ophiolitic peridotites, Tibet - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang; Jia-Ning Zhu; Hong-Yu Li; Chuan-Zhou Liu (Chemical Geology, 2025)

Autografted hair follicles with dermal papilla removed promote wound repair and regeneration in Bama mini-pigs - Wenzi Liang; Chang Mai; Yuandong Yuan; Xiuwen Chen; Bozhi Cai; Na Ni; Chutong Zhuang; Changmin Lin; Keng Huang (Journal of Molecular Histology, 2025)

Land-use types impact soil ecosystem functions by altering the soil multitrophic biodiversity and interactions - Tian-Lun Zhang; Shao-Yang Zhang; Lu Wang; Da Lin; Bang Ni; Tian-Gui Cai; Shuai Du; Dong Zhu (Soil Ecology Letters, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

Integrating UAV and satellite LAI data into a modified DSSAT-rapeseed model to improve yield predictions - Chufeng Wang; Lin Ling; Jie Kuai; Jing Xie; Ni Ma; Liangzhi You; William D. Batchelor; Jian Zhang (Field Crops Research, 2025)

Electrochemical oxidation of methylene blue from high salinity dyeing wastewater by a novel reduced graphene oxide and La co-modified PbO2 electrode - Zepeng Sun; Lin Gan; Yashi Liu; Qipan Liu; Qian Gao; Yue Ni (Desalination, 2025)

Core-shell structured magnetic beads based on sodium alginate/chitosan for nitrogen removal enhancement - Han Zhang; Bolin Li; Cong Ding; Rui Ni; Xiangyu Lin (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Advances in Neuroprotective Mechanisms of Aerobic Exercise to Reduce the Risk of Glaucoma - Yaqian Qu; Jingquan Sun; Lin Li; Siyu Chen; Yihan Ni; Xiangdeng Lai; Wang Yi (Journal of Science in Sport and Exercise, 2025)

IMTFF-Networks: A deep learning model for cattle behavior classification integrating multimodal time-frequency features - Xinglin Ni; Zhenjie Hou; En Lin; Xing Li; Jiuzhen Liang; Xinwen Zhou (Applied Animal Behaviour Science, 2025)

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Long-term suppression of Microcystis aeruginosa by tannic acid: Risks of microcystin pollution and proteomic mechanisms - Li Yin; Kaipian Shi; Yu Yin; Yong Zhang; Lin Xu; Junfeng An; Chunqing Peng; Conghui Wang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Regulation mechanisms of tea residue-based carbon dots in water-induced full-color emission and applications of visual ratio water sensors in organic solvents and WLEDs - Chao Yong; Ying Lei; Jian Du; Yinghui Liu; Yu Li; Fan Ye; Lin Xu; Guobin Ni; Shaowu Zhang (Analytica Chimica Acta, 2025)

Revealing the underestimated role of Gram-positive bacteria in iron reduction within paddy soils - Yu Huang; Yuquan Tan; Lin Shen; Chao Peng; Yaying Li; Juntao Zhang; Fengrong Zhang; Chunlin Ni; Wei Liu; Yundang Wu; Fangbai Li (Science of The Total Environment, 2025)

Spatial variability of groundwater flow fields caused by nonstationary random input parameter processes - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Journal of Hydrology, 2025)

Uncovering toxin production and molecular-level responses in Microcystis aeruginosa exposed to the flame retardant Tetrabromobisphenol A - Li Yin; Yu Yin; Lin Xu; Yong Zhang; Kaipian Shi; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Improvement of stability and antioxidant capacity of peptide - iron complexes by sonication - Dong Lin; Yongqing Zhang; Qinqin Xiong; Liyun Zhang; Sha Cheng; Jia Yu; Mashaal Ahmad; Yalin Ni; Su Xu; Heng Luo (Food Chemistry, 2025)

Efficient and stable extraction of nano-sized plastic particles enabled by bio-inspired magnetic “robots” in water - Yanpeng Cai; Buyun Zheng; Xiaofeng Lin; Xin You; Qunpo Jia; Ni Xue (Environmental Pollution, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

AFB1 consolidates HBV harm to induce liver injury and carcinogenic risk by inactivating FTCD-AS1-PXR-MASP1 axis - Yaqi Xing; Wusheng Zhong; Xuejun Wu; Zhengzhong Ni; Wenya Lv; Ying Fan; Ling Chen; Haorui Lin; Yangmin Xie; Jianwei Lin; Yongdong Niu (Toxicology, 2025)

Remnants of a Jurassic marginal sea plate in the Meso-Tethyan Ocean revealed by multi-stage magmatism in the Lagkorco ophiolite, Central Tibet - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Xiao-Ni Li; Zhen-Yu Zhang; Zhen Zhang; Yin-Zheng Lin (Lithos, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

A procedure to simulate spread of post-earthquake fire in urban area considering seismic damage to buildings - Qi Wang; Xuchuan Lin; Shuna Ni; Jiangrong Zhong; Ning Yang (Natural Hazards, 2025)

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Recycled calcium polypeptides modulate microbial dynamics and enhance bioconversion in kitchen waste-garden waste co-composting system - Xiaowen Sun; Zhe Li; Zhi Li; Yongxuan Liu; Jie Zeng; Tan Wang; Hong Ni; Lin Li (Journal of Environmental Management, 2025)

pH-dependent medium-chain fatty acid synthesis in waste activated sludge fermentation: Metabolic pathway regulation - Yun Wang; Shu-Lin Wu; Wei Wei; Lan Wu; Sansi Huang; Xiaohu Dai; Bing-Jie Ni (Journal of Environmental Management, 2025)

Influence of different oxides on the combustion process of nano aluminum - Chunlong Jiang; Haobo Bi; Qizhao Lin; Zhanshi Ni (Fuel, 2025)

Establishment of appropriate conditions for the efficient determination of multiple mycotoxins in tea samples and assessment of their drinking risks - Ying-Chun Wan; Zwe-Lin Kong; Yi-Hsieng Samuel Wu; Chien-Ni Huang; Tomohisa Ogawa; Jau-Tien Lin; Deng-Jye Yang (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Organonickel complex J-aggregation on interfacial evaporator promotes broadband absorption and salt rejection for efficient solar-powered desalination - Yi-Ting Lin; Joanna S. Lin; Yung-Cong Yang; Jen-Shyang Ni (Desalination, 2025)

Selective separation and value-added utilization of non-metallic components from waste mobile phone circuit boards for reinforcing epoxy composites - Jie Zhang; Zhengxin Peng; Jiang Wang; Hao Yang; Honghai Chen; Lin Zhuo; Qiaoling Liu; Ni Luo; Yi Zhou; Yutong Yan; Changji Yang (Chemical Engineering Journal, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Mechanistic insights into the impact of calcium and magnesium ions on ferrous sulfide aggregation and reducing activity - Kaipian Shi; Li Yin; Junfeng An; Lin Xu; Chunqing Peng; Yong Zhang; Yuechun Zeng; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Chemical Engineering Journal, 2025)

Correction: The origin of summer high-salinity water in the southern Bay of Bengal and its interannual variabilities - Xinyu Lin; Yun Qiu; Wenshu Lin; Xutao Ni; Chunsheng Jing (Climate Dynamics, 2025)

Construction of an adverse outcome pathway for the cardiac toxicity of bisphenol a by using bioinformatics analysis - Leyan Zhang; Lin Tian; Baofang Liang; Liang Wang; Shuzhen Huang; Yongru Zhou; Mengmei Ni; Lishi Zhang; Yun Li; Jinyao Chen; Xiaomeng Li (Toxicology, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Efficient degradation of chloroquine via pyrite-modified electro-Fenton yielding •OH and O2•- - Yuehua Zhang; Yinghui Lin; Yuanji Shi; Linyan Yang; Bing-Jie Ni; Xueming Chen (Journal of Cleaner Production, 2024)

Effects of microplastics on soil physicochemical properties and vertical migration and transformation of chromium - Jia-li Li; Na-ying Li; Jia Ni; Rui-lin Wan; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2024)

Investigating dehumidification and heating performance in a dual evaporator heat pump system for electric vehicles - Kang Li; Mingfei Tan; Yuan Man; Hua Zhang; Binlin Dou; Ni Liu; Tianjiao Zhang; Qize He; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

The mining of thermostable β-glucosidase for tea aroma enhancement under brewing conditions - Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Yongquan Xu; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Fe (hydr)oxides and organic colloids mediate colloid-bound chromium mobilization in Cr(VI) contaminated paddy soil - Ting Liu; Ran Wei; Jingjing Li; Weipeng Xie; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Environmental Pollution, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

Level of Service Evaluation Method for Waterway Intersections - Yihua Liu; Xin Guo; Fei Lin; Nian Liu; Daiheng Ni (Journal of Marine Science and Engineering, 2024)
Waterway intersections pose significant risks for vessel navigation due to the complexities of operational conditions in these areas. The lack of clear collision avoidance rules, combined with ineffective communication, exacerbates these dangers. To address this issue, transportation authorities will typically employ flow organization strategies to optimize operations at these intersections. However, effective methods for traffic management, both before and after implementation, are still lacking. This paper proposes a methodology to determine the level of service (LOS) needed for waterway intersections by using the degree of conflict during vessel navigation as a performance measure, while also considering the unique characteristics of vessel encounters in these areas. The methodology was applied to analyze the Yuxingnao waterway, and the results demonstrate its effectiveness in assessing operational conditions and providing a clear classification of service levels over specific time periods. Consequently, this methodology not only enables transportation authorities to evaluate the effectiveness of traffic management strategies, such as route planning and traffic organization, but also helps predict the impact of potential improvement countermeasures.

Trajectory of antibiotic resistome response to antibiotics gradients: A comparative study from pharmaceutical and associated wastewater treatment plants to receiving river - Na Wang; Shuchang Li; Mali Shi; Ni Ni; Xiaohui Zhang; Xinyan Guo; Huai Lin; Yi Luo (Water Research, 2024)

A simplified analytical solution of pipeline response under normal faulting - Jianfeng Li; Xiaogang Qin; Mingge Ye; Qingshu Chen; Pengpeng Ni; Cungang Lin (Tunnelling and Underground Space Technology, 2024)

Carbon reduction benefits of photovoltaic-green roofs and their climate change mitigation potential: A case study of Xiamen city - Taoyu Chen; Ni Zhang; Zubin Ye; Kunneng Jiang; Zhiqian Lin; Huimin Zhang; Yanhui Xu; Qunyue Liu; He Huang (Sustainable Cities and Society, 2024)

Green energy meets urban agriculture: Unveiling the carbon reduction potential of Rooftop Agrivoltaics - Qunyue Liu; Taoyu Chen; Ni Zhang; Zubin Ye; Kunneng Jiang; Zhiqian Lin; Yaling Gao; Yourui Guo; Aifang Weng (Journal of Cleaner Production, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Surface S doping induced ladder-regulation of lattice oxygen on the vertical FeCoOOH for water oxidation - Ning Yu; Ren-Ni Luan; Chao-Yue Gu; Yi-Lin Dong; Guanqun Han; Han Hu; Bin Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Exploration of the flavor diversity of oolong teas: A comprehensive analysis using metabolomics, quantification techniques, and sensory evaluation - Xiaoxiao Feng; Haoli Wang; Yashu Yu; Yiwen Zhu; Jingke Ma; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Food Research International, 2024)

Large variability in permafrost degradation over the Northern Hemisphere - Guojie Hu; Lin Zhao; Defu Zou; Xiaodong Wu; Ren Li; Xiaofan Zhu; Youqi Su; Tonghua Wu; Yifan Wu; Jie Ni (CATENA, 2024)

Stimulation of organic N mineralization by N‒acquiring enzyme activity alleviates soil microbial N limitation following afforestation in subtropical karst areas - Lijun Liu; Qilin Zhu; Dongni Wen; Lin Yang; Kang Ni; Xingliang Xu; Jianhua Cao; Lei Meng; Jinling Yang; Jinxing Zhou; Tongbin Zhu; Christoph Müller (Plant and Soil, 2024)

A study on the transfer of radionuclides and of the resulting radiation dose assessment for marine organisms on the eastern coast of Yantai city - Jialin Ni; Dongjun Chen; Zhen Qian; Jing Lin; Feng Lin; Jianda Ji; Dekun Huang; Tao Yu (Frontiers in Marine Science, 2024)
Oceans are repositories of radionuclides. Radionuclides are transferred through the food chain and cause ionizing radiation hazards for marine organisms. In this study, the transfer characteristics of 226 Ra, 40 K, 14 C, 3 H, 137 Cs and 90 Sr in organisms at different trophic levels in the eastern coast of Yantai city were investigated. The risk of ionizing radiation to organisms was assessed using the ERICA Tool 2.0. The results show no significant changes in the concentration of any of the nuclides in the coastal area compared to the preoperation period of the nuclear power plant. The transfer factor of 137 Cs, 40 K, 226 Ra, 14 C, 90 Sr and 3 H at the different trophic levels of marine organisms were 2.09, 1.29, 1.17, 1.15, 1.06 and 0.74, respectively. The dose rates of ionizing radiation to organisms from six radionuclides ranged from 32.02 nGy·h -1 to 195.49 nGy·h -1 and had a mean value of 102.86 ± 57.30 nGy·h -1 . The main artificial radionuclides ( 14 C, 3 H, 90 Sr, 137 Cs) released by nuclear power plants in the study area produced negligible radiation doses to marine organisms. However, other artificial radionuclides present in the effluents of nuclear power plants ( 99 Tc, 110m Ag and 131 I) as well as other natural radionuclides (includes 210 Po, 210 Pb, etc) were not included, and further evaluation of these is recommended.

An Intelligent Indicator Film Based on Food Derived Materials for Real-Time Visual Monitoring of Salmon Freshness - Zhiyu Yan; Siqi Zhang; Songyi Lin; Ni Ding; Jiaxin Qiang; Tongtong Xie; Simin Zhang (Journal of Aquatic Food Product Technology, 2024)

Human impacts overwhelmed climate as the dominant factor controlling lacustrine organic matter accumulation in Erhai Lake 2000 years ago, Southwest China - Durui Lin; Enlou Zhang; Enfeng Liu; Weiwei Sun; Rong Wang; Xianqiang Meng; Zhenyu Ni; Yao Wang; Yang You (Science of The Total Environment, 2024)

Efficient degradation and mineralization of polyethylene terephthalate microplastics by the synergy of sulfate and hydroxyl radicals in a heterogeneous electro-Fenton-activated persulfate oxidation system - Yinghui Lin; Yuehua Zhang; Yonghao Wang; Yuancai Lv; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2024)

Analysis the sewage sludge recycling strategy based on real-time pyrolysis performance and pyrochar characteristics - Jingjing Chen; Yuping Zheng; Mengyan Lv; Tingting Zhao; Qingqi Lin; Zhuobiao Ni; Zuotai Zhang; Rongliang Qiu (Journal of Cleaner Production, 2024)

κ-Carrageenan masking bitterness perception in surimi gels containing potassium chloride-based salt substitutes: Gel properties, oral processing, and sensory evaluation - Ni He; Xinran Chen; Lin Li; Shaoyun Wang; Meijuan Lan; Yi Yuan; Zhenhui Zhang; Tongshuai Li; Xia Zhang; Xing He; Bing Li (Food Chemistry, 2024)

Green energy and rooftop innovation: Unlocking the carbon reduction potential of photovoltaic-green roofs - Taoyu Chen; Zubin Ye; Kunneng Jiang; Ni Zhang; Zhiqian Lin; Qunyue Liu; Yourui Guo; He Huang (Energy and Buildings, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

Unveiling the versatile performance of transition metal sulfides in peroxymonosulfate activation - Zhifang Zhao; Lin Lin; Shanshan Liu; Yiqian Chen; Sanford V. Daniels; Zijian Xu; Zhenhua Chen; Haitao Li; Yanqing Wu; Lingling Guo; Qiteng Zheng; Zhenhua Duan; et al. (Chemical Engineering Journal, 2024)

The value of histopathologic examination and Xpert (MTB/RIF) assay in diagnosis of cervical lymph node tuberculosis after coarse needle biopsy guided by CEUS: a retrospective analysis of 612 cases - Wenzhi Zhang; Jianping Xu; Lin Zhang; Tu Ni (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objective To investigate the value of histopathological examination (HPE) and Xpert Mycobacterium tuberculosis bacilli/rifampicin (MTB/RIF) assay in diagnosis of cervical lymph node tuberculosis (LN TB) after coarse needle biopsy (CNB). Methods We retrospectively analyzed 612 samples obtained from October 2017 to August 2023 from patients suspected cervical LN TB with surgically pathological, microbial culture confirmed, and clinically confirmed cervical lymph node enlargement who received ultrasound-guided CNB assisted by contrast-enhanced ultrasound (CEUS) at our hospital. All specimens were assessed by HPE and the Xpert (MTB/RIF) assay. We analyzed the results to determine the diagnostic value of HPE and Xpert (MTB/RIF) assay in samples taken after CEUS-assisted CNB of LN TB, and to evaluate the safety of CNB. Results Based on the comprehensive reference standard established in this study, 532 of 612 patients were diagnosed with cervical LN TB, of which 476 were CNB positive cases, the positive rate of diagnosis was 89.5%。The sensitivity, specificity, positive predictive value, negative and predictive value of HPE were 80.4%, 91.2%, 98.4%, 41.2% respectively, while those of the Xpert MTB/RIF assay were 75.7%, 98.7%, 99.7%, 38.0% respectively. No postoperative complications were noted, and the Clavien–Dindo grade was 2. Conclusion CEUS-assisted CNB has high diagnostic value and is safe for cervical LN TB. The sensitivity of HPE is slightly higher than that of Xpert (MTB/RIF) assay, and the specificity of Xpert (MTB/RIF) assay is higher than that of HPE, so Xpert (MTB/RIF) assay can correct the cervical lymph node tuberculosis with negative HPE.

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

Impact of Inclined Fault and Spherical Cavity on Sandstone Failure and Acoustic Response Under Triaxial Compression - Yusong Zhao; Zi Lin; Anna Ni; Chencheng Lin (Geotechnical and Geological Engineering, 2024)

The origin of summer high-salinity water in the southern Bay of Bengal and its interannual variabilities - Xinyu Lin; Yun Qiu; Wenshu Lin; Xutao Ni; Chunsheng Jing (Climate Dynamics, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

Slope displacement prediction based on multisource domain transfer learning for insufficient sample data - Hai-Qing Zheng; Lin-Ni Hu; Xiao-Yun Sun; Yu Zhang; Shen-Yi Jin (Applied Geophysics, 2024)

Warming stimulates mangrove carbon sequestration in rising sea level at their northern limit: An in situ simulation - Peiyang Qiao; Ying Dong; Xiaoxuan Gu; Lian Xu; Mei Li; Wandong Chen; Li Lin; Xiaopin Ni; Luzhen Chen (Limnology and Oceanography, 2024)
Global warming and sea‐level rise are directly influencing the growth, distribution, and greenhouse gas emissions of mangrove forests. However, mangrove forests growing at their latitudinal limits are relatively susceptible to warming; nevertheless, few studies have focused on GHG emissions of latitudinal limits mangrove forests as related to global climate change. To address this knowledge gap, a multiyear in situ control experiment was established in a restored plantation at the northern distribution limit of Kandelia obovata , the most cold‐tolerant mangrove species in China, to simulate both warming and sea‐level rise. We investigated the growth patterns and sediment greenhouse gas emissions of a K. obovata population and identified the primary factors contributing to these changes. The results showed that warming and moderate sea‐level rise enhanced biomass by more than 18%, indicating that warming stimulated plant growth while excessive sea‐level rise inhibited it. The sediment greenhouse gas emissions ranged from 45.5 to 484.6 mgCO 2 m −2 h −1 , 5.6 to 590.3 μ gCH 4 m −2 h −1 , and 11.4 to 385 μ gN 2 O m −2 h −1 , which increased with warming while decreased with sea‐level rise, acting as the net source of greenhouse gas emission. Our study predicted that sea‐level rise, while directly changing sediment properties, had combined effects with warming on these studied mangrove forests that were predicted to emit more greenhouse gases from sediments in the future. These findings indicated that K. obovata plantations within their latitudinal limits tend to accumulate more CO 2 for biomass carbon storage under warming conditions, while stimulating sediment greenhouse gas emissions, which will offset their climate mitigating effect in future climatic scenarios.

Best Practices for Development and Validation of Enzymatic Activity Assays to Support Drug Development for Inborn Errors of Metabolism and Biomarker Assessment - Mitra Azadeh; Jeremy Good; Michele Gunsior; Nadia Kulagina; Yanmei Lu; Jim McNally; Heather Myler; Yan G. Ni; Ryan Pelto; Karen J. Quadrini; Catherine Vrentas; Lin Yang (The AAPS Journal, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Challenges and enhancement technologies of medium chain carboxylates production in open culture anaerobic fermentation - Shu-Lin Wu; Lan Wu; Wei Wei; Jiali Shentu; Yuyang Long; Dongsheng Shen; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Purification of gamma-cyclodextrin via selective coordination with potassium ions to form metal-organic frameworks - Libumo Baqing; Xiaojian He; Qijia Ni; Hanwen Zhang; Tianfu Li; Xueyuan Lin; Tao Guo; Bello Mubarak Garba; Xintao Chen; Jiwen Zhang; Can Peng; Caifen Wang; et al. (Carbohydrate Polymers, 2024)

Occurrence, seasonal variations, and spatial distributions of current-use organoamine pesticides in the atmosphere of Shanghai, China - Junkang Ni; Minghong Cai; YongJun Lin; Tong Li; Jing Ma (Atmospheric Pollution Research, 2024)

Human Amniotic Epithelial Stem Cells Alleviate Autoimmune Premature Ovarian Insufficiency in Mice by Targeting Granulosa Cells via AKT/ERK Pathways - Xiaohang Ye; Yifeng Lin; Yanyun Ying; Xuezhi Shen; Feida Ni; Feixia Wang; Jianpeng Chen; Wei Zhao; Xiaoming Yu; Dan Zhang; Yifeng Liu (Stem Cell Reviews and Reports, 2024)
Autoimmune factors play an important role in premature ovarian insufficiency (POI). Human amniotic epithelial stem cells (hAESCs) have recently shown promising treatment effects on chemotherapy-induced POI. However, the therapeutic efficacy and underlying mechanisms of hAESCs in autoimmune POI remain to be investigated. In this study, we showed for the first time that intravenous transplantation of hAESCs could reside in the ovary of zona pellucida 3 peptide (pZP3) induced autoimmune POI mice model for at least 4 weeks. hAESCs could improve ovarian function and fertility, alleviate inflammation and reduce apoptosis of granulosa cells (GCs) in autoimmune POI mice. The transcriptome analysis of mice ovaries and in vitro co-cultivation experiments suggest that activation of the AKT and ERK pathways may be the key mechanism in the therapeutic effect of hAESCs. Our work provides the theoretical and experimental foundation for optimizing the administration of hAESCs, as well as the clinical application of hAESCs in autoimmune POI patients. Graphical Abstract

Tessaracoccus lacteus sp. nov., Isolated from the Sludge of a Wastewater Treatment Plant - Jialin Tan; Kaiqing Yang; Gengbo Jiang; Zhuobiao Ni; Qingqi Lin; Zhepu Ruan; Rongliang Qiu (Current Microbiology, 2024)

Evolution characteristics and mechanisms of the spring warm pool in the Bay of Bengal - Wenshu Lin; Yun Qiu; Xutao Ni; Xinyu Lin; Tongtong Liu (Frontiers in Marine Science, 2024)
Knowledge of spring warm pool in the Bay of Bengal (BoBWP) is key for further understanding the climate variability in this region and beyond, but little is known about the BoBWP climatological state and the related mechanisms. In this study, we investigate the spatial structure and evolution of the BoBWP using daily Optimum Interpolation SST data from 1982-2022 in combination with multi-source data. Our analysis shows that the BoBWP is located in the central bay (6°-13°N) with a thickness around 20 m ~ 40 m. Composite analysis indicates that the BoBWP emerges in early April, peaks in early May and dissipates in early June. During the developing period, the net heat flux dominates the formation of spring warm pool through significant air-sea coupling processes, and induces the warming rate of 0.27°C/10d in the mixed layer, which is far larger than the contribution of oceanic dynamical processes (0.01°C/10d). During the decaying period, the net heat flux also plays a dominant role, with a cooling rate of -0.21°C/10d, meanwhile ocean dynamical processes contribute to the cooling of the warm pool with a rate of -0.01°C/10d. Additionally, the SST and the area of the BoBWP are significantly correlated with ENSO (r=0.66 and 0.73, p=0.05). During El Niño decaying year, the BoBWP primarily expands in a southward direction, with a 75% increase in area. Conversely, during La Niña decaying year, the BoBWP almost disappears, with a 52% decrease.

Post-cyclic undrained behavior of marine soft clay subjected to partially drained cyclic loading - Junhao Tong; Qiang Wang; Weikang Zhang; Lin Guo; Dingyu Ni; Junli Zhai; Dongyang Yuan; Haozheng Wang (Marine Georesources & Geotechnology, 2024)

Resveratrol in disease prevention and health promotion: A role of the gut microbiome - Xuexiang Chen; Jing Zhang; Ni Yin; Prachi Wele; Fang Li; Soham Dave; Juanying Lin; Hang Xiao; Xian Wu (Critical Reviews in Food Science and Nutrition, 2024)

Co-occurrence of elevated arsenic and fluoride concentrations in Wuliangsu Lake: Implications for the genesis of poor-quality groundwater in the (paleo-)Huanghe (Yellow River) catchment, China - Ya-Ni Yan; Jun-Wen Zhang; Na Wu; Zi-Han Xia; Lin Liu; Zhi-Qi Zhao (Water Research, 2024)

Hydrodynamics and dissolved organic matter components shaped the fate of dissolved heavy metals in an intensely anthropogenically disturbed estuary - Ling Zhang; Yunchao Wu; Jinlong Li; Zhixin Ni; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Science of The Total Environment, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

Complete long-term monitoring of greenhouse gas emissions from a full-scale industrial wastewater treatment plant with different cover configurations - Qinyi Wang; Yangyue Sheng; Yili Zhang; Xinrun Zhong; Hui Liu; Zhengfeng Huang; Dan Li; Hao Wu; Yuanzhi Ni; Junqi Zhang; Weiqing Lin; Kaipei Qiu; et al. (Journal of Environmental Management, 2024)

Efficiencies of filtration sampling and extraction for recovery of viable Staphylococcus aureus bioaerosols - Ching-Wen Chang; Yen-Ni Lin; Sheng-Hsiu Huang; Yu-Ju Horng (Journal of Aerosol Science, 2024)

Production of novel mung bean peptides-based zinc supplement: Process optimization, chelation mechanism, and stability assessment in vitro - Liyun Zhang; Yinxia Wang; Yalin Ni; Yongqing Zhang; Yongling Liu; Bin Du; Heng Luo; Dong Lin (Food Bioscience, 2024)

Description and Genomic Characteristics of Diaphorobacter limosus sp. nov., Isolated from a Sewage-Treatment Plant - Kaiqing Yang; Jialin Tan; Gengbo Jiang; Zhuobiao Ni; Qingqi Lin; Yuanqing Chao; Zhepu Ruan; Rongliang Qiu (Current Microbiology, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Green synthesis of Fe3O4@ceramsite from sludge improving anaerobic digestion performance of waste activated sludge - Pengqu Zhang; Dongsheng Shen; Jinyang Shao; Xiaoyu He; Jianjun Zeng; Shu-Lin Wu; Yuyang Long; Wei Wei; Bing-Jie Ni (Journal of Environmental Management, 2024)

Insights into the phage community structure and potential function in silage fermentation - Yuan Wang; Yu Gao; Xin Wang; Yanli Lin; Gang Xu; Fuyu Yang; Kuikui Ni (Journal of Environmental Management, 2024)

Influence of plasma breakdown on pores and fractures in bituminous coal: A new characterization method of breakdown energy - Youping Xu; Zhen Ni; Baiquan Lin (Gas Science and Engineering, 2024)

Metabolomics analysis of physicochemical properties associated with freshness degradation in frozen Antarctic krill (Euphausia superba) - Ling Ni; Chaojun Jiang; Quanyou Guo; Hai Chi; Chengqi Fan; Jiangao Shi; Na Lin; Zhidong Liu; Shengjun Chen (Food Research International, 2024)

Toosendanin induces hepatotoxicity via disrupting LXRα/Lipin1/SREBP1 mediated lipid metabolism - Sixin Chen; Jiajie Ni; Li Luo; Jinxian Lin; Hongjie Peng; Feihai Shen; Zhiying Huang (Food and Chemical Toxicology, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

Damage analysis of buried pipelines subjected to side-by-side twin tunneling based on centrifuge and numerical modeling - Wei Sun; Enpeng Lin; Zhiqiang Yang; Pengpeng Ni; Yu Chen (Tunnelling and Underground Space Technology, 2024)

Toosendanin induces hepatotoxicity by restraining autophagy and lysosomal function through inhibiting STAT3/CTSC axis - Li Luo; Jiajie Ni; Jiahui Zhang; Jinxian Lin; Sixin Chen; Feihai Shen; Zhiying Huang (Toxicology Letters, 2024)

Efficacy and mechanism of copper removal from electroplating wastewater by schwertmannite-like mineral - Ni Li; Mingyan Shi; Yimiao Lan; Hongguo Zhang; Guanfeng An; Shaonan Lin; Langming Xue (Journal of Environmental Chemical Engineering, 2024)

Recyclable bactericidal packaging films for emperor banana preservation - Wanmei Lin; Jingyao Wang; Mengyi Wang; Zhonghong Li; Yongsheng Ni; Jianlong Wang (Food Chemistry, 2024)

Viral community distribution, assembly mechanism, and associated hosts in an industrial park wastewater treatment plant - Wenqing Hong; Hong Mei; Xianyang Shi; Xiaoxing Lin; Shuijing Wang; Renjie Ni; Yan Wang; Liyan Song (Environmental Research, 2024)

Stochastic Quantification of Spatial Variability of Flow Fields in Heterogeneous, Non-uniform, Confined Aquifers - Chuen-Fa Ni; Ching-Min Chang; Chi-Ping Lin; I-Hsian Lee (Transport in Porous Media, 2024)

Community Structure and Water Quality Assessment of Benthic Macroinvertebrates in Hongze Lake - Lixiao Ni; Lin Zhou; Amar Ali Adam Hamad; Chu Xu; Wenlu Sang; Cunhao Du; Yun Nie; Haoyue Li; Jiahui Shi; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Variability in the displacement of solute particles in heterogeneous confined aquifers - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Advances in Water Resources, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Competitive enrichment of comammox Nitrospira in floccular sludge - Jiaying Hou; Ying Zhu; Jinzhong Liu; Limin Lin; Min Zheng; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Water Research, 2024)

Spatial and temporal variations of surface background ozone in China analyzed with the grid-stretching capability of GEOS-Chem High Performance - Xingpei Ye; Lin Zhang; Xiaolin Wang; Xiao Lu; Zhongjing Jiang; Ni Lu; Danyang Li; Jiayu Xu (Science of The Total Environment, 2024)

Does a hydropower reservoir cascade really harm downstream nutrient regimes - Qiuwen Chen; Yuchen Chen; Yuqing Lin; Jianyun Zhang; Jinren Ni; Jun Xia; Lin Xiao; Tao Feng; Honghai Ma (Science Bulletin, 2024)

Seaward alteration of arsenic mobilization mechanisms based on fine-scale measurements in Pearl River estuarine sediments - Chunyang Zhou; Wei Lin; Zhaokui Ni; Fuqiang Fan; Yue Dong; Yue Gao; Willy Baeyens; Shengrui Wang (Journal of Hazardous Materials, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Nanoplastic propels diet-induced NAFL to NASH via ER-mitochondrial tether-controlled redox switch - Jie Wei; Jintao Liu; Huan Wang; Kai Wen; Xiuye Ni; Yilong Lin; Jingru Huang; Xiang You; Zhao Lei; Juan Li; Heqing Shen; Yi Lin (Journal of Hazardous Materials, 2024)

Multidimensional exploration of the bitterness amelioration effect of roasting on Wuyi Rock tea - Weiying Su; Li Ni; Yizhe Chen; Daoliang Wang; Chih-Cheng Lin; Yuan Liu; Zhibin Liu (Food Chemistry, 2024)

Development of a sensitive simultaneous analytical method for 26 targeted mycotoxins in coix seed and Monte Carlo simulation-based exposure risk assessment for local population - Chuiwei Liu; Weisheng Xu; Lei Ni; Huafeng Chen; Xiangju Hu; Honglin Lin (Food Chemistry, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Anti-CD20 treatment attenuates Th2 cell responses: implications for the role of lung follicular mature B cells in the asthmatic mice - Jilong He; Jingling Li; Qibin Lin; Haiyang Ni; Sisi Huang; Hong Cheng; Xuhong Ding; Yi Huang; Hongying Yu; Yaqing Xu; Hanxiang Nie (Inflammation Research, 2024)

Rapid identification and characterization of pineapple fruitlet core rot pathogens on the ‘TN20’ cultivar in Taiwan - Yu-Ping Liang; Kuan-Yu Lin; Su-Yu Lai; Hui-Fang Ni (European Journal of Plant Pathology, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

Direct and indirect consumption activities drive distinct urban-rural inequalities in air pollution-related mortality in China - Jingxu Wang; Jintai Lin; Yu Liu; Feng Wu; Ruijing Ni; Lulu Chen; Fangxuan Ren; Mingxi Du; Zhongyi Li; Haoyu Zhang; Zhengzhong Liu (Science Bulletin, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Effect of lignin on coal slime combustion characteristics and carbon dioxide emission - Zhanshi Ni; Haobo Bi; Hao Shi; Xiang Liu; Junjian Tian; Yurou Yao; Liqun He; Kesheng Meng; Qizhao Lin (Journal of Cleaner Production, 2024)

Enhanced biomethane production from waste activated sludge anaerobic digestion by ceramsite and amended Fe2O3 ceramsite - Dongsheng Shen; Pengqu Zhang; Shu-Lin Wu; Yuyang Long; Wei Wei; Bing-Jie Ni (Journal of Environmental Management, 2024)

A novel family of W-doped Bi0.5Sr0.5FeO3-δ perovskite as oxygen electrode catalyst for CO2 electrolysis in solid oxide electrolysis cells - Zhenfei Li; Hui Ye; Pengkai Shan; Qing Ni; Lin Sun; Yifeng Zheng (Fuel, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Topography-driven differences in soil N transformation constrain N availability in karst ecosystems - Dongni Wen; Lin Yang; Kang Ni; Xingliang Xu; Longfei Yu; Ahmed S. Elrys; Lei Meng; Jinxing Zhou; Tongbin Zhu; Christoph Müller (Science of The Total Environment, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Biorefinery of flavonoid aglycones using acidic natural deep eutectic solvents: Role of Bronsted acids and application in valorization of Sophora japonica buds waste - Yishu Ni; Lin Zhu; Shuhui Ye; Xiafeng Xu; Xianrui Liang; Sheng Fang (Food and Bioproducts Processing, 2024)

Adapting to seasonal temperature variations: A dynamic multi-subunit strategy for sulfur autotrophic denitrification bioreactors - Yi-Lu Sun; Han-Lin Wang; Huu Hao Ngo; Wenshan Guo; Bing-Jie Ni; Xue-Ning Zhang; Wei Wei (Environmental Research, 2024)

The characteristics of noise propagation and distribution on the ultra-wide cross section of highways: A case study in Guangdong Province - Xiaochun Qin; Yanhua Li; Lin Ma; Yuping Zhang; Anchen Ni; Vicky Wangechi Wangari (Environmental Impact Assessment Review, 2024)

Carboxymethyl cellulose-based supramolecular hydrogel with thermo-responsive gel-sol transition for temporary plugging of oil pipeline in hot work - Ziteng Yang; Ruixuan Ni; Yang Yang; Jie Qi; Xingyu Lin; Yong Zhang; Li Wang; Yuanpeng Wu; Xiaojiang Li; Hongsheng Lu (Carbohydrate Polymers, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Short-Term Efficacy of Cerebello-spinal tDCS and Body Weight-Supported Treadmill Training in the Hypertrophic Olivary Degeneration: a Rare Case Report - Xi-Chen Wang; Nai-Qing Cai; Xiao-Ping Cheng; Lin Zhang; Wen-Zong Wang; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2023)

Planktonic/benthic Bathyarchaeota as a “gatekeeper” enhance archaeal nonrandom co-existence and deterministic assembling in the Yangtze River - Shufeng Liu; Yahsuan Lin; Tang Liu; Xuming Xu; Jiawen Wang; Qian Chen; Weiling Sun; Chenyuan Dang; Jinren Ni (Water Research, 2023)

An analytical solution for landslide impact on buried continuous pipelines - Mingge Ye; Xiaogang Qin; Jianqiang Liu; Jianfeng Li; Pengpeng Ni; Cungang Lin (Tunnelling and Underground Space Technology, 2023)

Antibiotics inhibit methanogenesis during municipal solid waste decomposition - Renjie Ni; Shuijing Wang; Xiaoxing Lin; Liyan Song (Science of The Total Environment, 2023)

Ioxynil and diethylstilbestrol impair cardiac performance and shell growth in the mussel Mytilus coruscus - Yi-Feng Li; Yue-Tong Lin; Yu-Qing Wang; Ji-Yue Ni; Deborah M. Power (Science of The Total Environment, 2023)

Anthropogenic activities altering the ecosystem in Lake Yamzhog Yumco, southern Qinghai-Tibetan Plateau - Wu Han; Enlou Zhang; Weiwei Sun; Qi Lin; Xianqiang Meng; Zhenyu Ni; Dongliang Ning; Ji Shen (Science of The Total Environment, 2023)

Effect of hydraulic regime on sulfur-packed bed performance: Denitrification and disproportionation - Yi-Lu Sun; Wei Wei; Huu Hao Ngo; Wen Shan Guo; Xue-Ning Zhang; Bing-Jie Ni; Wei-Qin Zhuang; Han-Lin Wang (Environmental Research, 2023)

Proteomic Analysis of the Amygdala Reveals Dynamic Changes in Glutamate Transporter-1 During Progression of Complete Freund’s Adjuvant-Induced Pain Aversion - Yuanyuan Wu; Yuerong Chen; Yunyun Xu; Wenqin Ni; Chalian Lin; Xiaomei Shao; Zui Shen; Xiaofen He; Chao Wang; Jianqiao Fang (Molecular Neurobiology, 2023)
Pain sufferer usually show an aversion to the environment associated with pain, identified as pain aversion. The amygdala, an almond-shaped limbic structure in the medial temporal lobe, exerts a critical effect on emotion and pain formation. However, studies on inflammatory pain-induced aversion are still relatively limited, and the available evidence is not enough to clarify its inherent mechanisms. Proteomics is a high-throughput, comprehensive, and objective study method that compares the similarities and differences of protein expression under different conditions to screen potential targets. The current study aimed to identify potential pivotal proteins in the amygdala of rats after complete Freund’s adjuvant (CFA)-induced pain aversion via proteomics analysis. Immunohistochemistry was performed to confirm the expression of glutamate transporter-1 (GLT-1) in the amygdala during different periods of pain aversion. Thirteen proteins were found to be different between the day 2 and day 15 groups. Among the 13 differentially expressed proteins, Q8R64 denotes GLT-1, which utilises synaptic glutamate to remain optimal extracellular glutamic levels, thereby preventing accumulation in the synaptic cleft and consequent excitotoxicity. The variation in GLT-1 expression was correlated with the variation tendency of pain aversion, which implies a potential link between the modulation of pain aversion and the excitability of glutamatergic neurons. This study demonstrated that exposure to inflammatory pain results in aversion induced from pain, leading to extensive biological changes in the amygdala.

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Structural characteristics of zooplankton communities in Hongze Lake driven by water environmental factors from 2016 to 2020 - Lixiao Ni; Haoyue Li; Lin Zhou; Jiahui Shi; Yun Nie; Feng Zhao; Shiyin Li (Environmental Monitoring and Assessment, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Soil calcium constrains nitrogen mineralization and nitrification rates in subtropical karst regions - Shuting Yang; Lin Yang; Dongni Wen; Lijun Liu; Kang Ni; Jianhua Cao; Tongbin Zhu; Christoph Müller (Soil Biology and Biochemistry, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Coordinating energy and material efficiency strategies for decarbonizing China's iron and steel sector - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Understanding the drivers of CO2 growth in China's iron and steel sector: An integrated analysis of the energy–material–economy nexus - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

In-situ production of lactate driving the biotransformation of waste activated sludge to medium-chain fatty acid - Shu-Lin Wu; Wei Wei; Huu Hao Ngo; Wenshan Guo; Chen Wang; Yun Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Variability of travel time of solute particles in single fractures with spatially variable aperture - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Engineering Geology, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Co-electron donors driven medium-chain fatty acids production: Roles of electron donors, reaction kinetics and metabolic pathways - Shu-Lin Wu; Yuyang Long; Wei Wei; Xingdong Shi; Dongsheng Shen; Bing-Jie Ni (Chemosphere, 2023)

How will China's steel demand develop under the investment-driven patterns? Integrating extended input-output model with dynamic steel flow analysis - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Surface fabrication of silica aerogels from inorganic precursor achieving elastic and superhydrophobic sponges for oil-water separation - Xiang Li; Xiaoxiao Huang; Qingge Feng; Zheng Liu; Dongbo Wang; Dachao Ma; Lin Feng; Chen Zuo; Junyi Liu; Sinan Wang; Zhuoyan Huang; Xiaodie Cheng; et al. (Journal of Environmental Chemical Engineering, 2023)

Occurrence and carcinogenic risk assessment of N-nitrosamines in some dried aquatic products in China - Siting Huang; Wusheng Fu; Qinmei Fang; Lei Ni; Renjin Zheng; Ling Yong; Zheng Huang; Jie Pang; Zhong Lin; Honglin Lin; Rongde Dai (Food Control, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Nano zero-valent iron enhances the absorption and transport of chromium in rice (Oryza sativa L.): Implication for Cr risks management in paddy fields - Ting Liu; Zeting Guan; Jingjing Li; Ming Ao; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

How to extend the lifetime of RO membrane? From the perspective of the end-of-life RO membrane autopsy - Jinyan Wang; Jingrun Xing; Ge Li; Zhikan Yao; Zhen Ni; Jing Wang; Songmiao Liang; Zhijun Zhou; Lin Zhang (Desalination, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Eco-physiological response mechanism of Tamarix chinensis to soil water changes in coastal wetlands of the Yellow River Delta - Peili Mao; Qingzhi Lin; Yuanxiang Pang; Kexin Wang; Ruiqiang Ni; Xin Han; Banghua Cao (Frontiers in Marine Science, 2023)
Elucidating the effect of soil moisture on the adaptation of dominant plants in coastal wetlands is important for predicting the evolution of vegetation in the region. In this paper, Tamarix chinensis , a dominant species in the Yellow River Delta, was used as the object to study the changes of its growth and physiological parameters with increasing soil salinity under different moisture conditions (normal watering, persistent drought and persistent waterlogging). Different salt stress (2‰, 5‰, 8‰, 12‰, 16‰, and 20‰) using pot experiments was also used to reveal the mechanism of soil moisture on its salt tolerance. The results showed that the relative growth rate between 5‰-8‰ soil salinity was the largest, and growth was significantly inhibited above 20‰. Among different moisture conditions, the difference in relative growth rate under normal watering and persistent drought were nonsignificant, while both were significantly lower than those under persistent waterlogging. With increasing soil salinity, relative water content and total chlorophyll content significantly decreased, and cell membrane permeability (malondialdehyde), sodium ion, osmoregulatory substances (proline, soluble protein), and protective enzyme activity (SOD) significantly increased, while changes in non-structural carbohydrates (NSC) were not significant. Compared with normal watering and persistent waterlogging, persistent drought had the lowest leaf relative water content, total chlorophyll content, and sodium ions, and the highest cell membrane permeability, osmoregulatory substances and protective enzyme activity. With increasing treatment time, the relative leaf water content and total chlorophyll content significantly decreased, and cell membrane permeability, osmoregulatory substances and protective enzyme activity increased more significantly than normal watering and persistent waterlogging. NSC increased under normal watering and persistent waterlogging, while significantly decreased under persistent drought. Correlation analysis showed that the relationships between sodium ions, total chlorophyll content and malondialdehyde were various under different moisture conditions. Under persistent drough, malondialdehyde was significantly positively correlated with relative conductivity, superoxide dismutase, proline, soluble protein and soluble sugar. Total chlorophyll content was the key indicator reflecting the salt and waterlogging tolerance of T. chinensis under normal watering and persistent waterlogging, while cell membrane damage was under persistent drought. In summary, T. chinensis has strong salt and waterlogging tolerance, but persistent drought with salt stress can have serious impacts on its growth and survival.

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

New insights on municipal solid waste (MSW) landfill plastisphere structure and function - Xiaoxing Lin; Shuijing Wang; Renjie Ni; Liyan Song (Science of The Total Environment, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

Three-Dimensional Climatological Structures of the Arabian Sea Eddies and Eddy-Induced Flux - Xinyu Lin; Yun Qiu; Xutao Ni; Wenshu Lin; Cherry Aung (Journal of Ocean University of China, 2023)

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Degradation of sulfolane-contaminated groundwater in a tubular microbial fuel cell-based electro-Fenton system: Performance, external resistance effects and microbial community - Chi-Wen Lin; Yen-Ni Tsai; Shu-Hui Liu; Ting-Jun Zhu (Journal of Water Process Engineering, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Study on combustion characteristics of nano-aluminum in different gas atmospheres and environment temperatures - Chunlong Jiang; Haobo Bi; Zhanshi Ni; Hao Sun; Hao Shi; Qizhao Lin (Fuel, 2023)

Dynamic change of the carotenoid metabolic pathway profile during oolong tea processing with supplementary LED light - Zixin Ni; Yun Yang; Yining Zhang; Qingcai Hu; Jiaqi Lin; Hongzheng Lin; Zhilong Hao; Yuefei Wang; Jihong Zhou; Yun Sun (Food Research International, 2023)

Preparation of micro-fibrillated cellulose fibers by a simple two-step refining process for paper- based flexible electronic devices - Chenglong Fu; Changmei Lin; Weipeng Zhang; Yaling Lin; Jinhong Xiu; Yonghao Ni; Liulian Huang (Chemical Engineering Journal, 2023)

Inpainting truncated areas of CT images based on generative adversarial networks with gated convolution for radiotherapy - Kai Xie; Liugang Gao; Heng Zhang; Sai Zhang; Qianyi Xi; Fan Zhang; Jiawei Sun; Tao Lin; Jianfeng Sui; Xinye Ni (Medical & Biological Engineering & Computing, 2023)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Crustal accretion in a slow-spreading center of Meso-Tethyan Ocean: Constraints from cumulates in the Dongco ophiolite (Central Tibet) - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Zhen Zhang; Yin-Zheng Lin; Chuan-Zhou Liu (Lithos, 2023)

Iron-modified biochar boosts anaerobic digestion of sulfamethoxazole pharmaceutical wastewater: Performance and microbial mechanism - Zhili Ni; Lilin Zhou; Ziyang Lin; Bin Kuang; Gefu Zhu; Jianbo Jia; Tao Wang (Journal of Hazardous Materials, 2023)

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Geostatistical inversion method based on seismic waveform similarity - Xue-Bin Ni; Jia-Jia Zhang; Kang Chen; Guang-Zhi Zhang; Bao-Li Wang; Zhuo-Fan Liu; Ying Lin (Applied Geophysics, 2023)

Role of roasting in the formation of characteristic aroma of wuyi rock tea - Sijia Zhan; Zhibin Liu; Weiying Su; Chih-Cheng Lin; Li Ni (Food Control, 2023)

Variable response of particles and inorganic carbon of two different soils during splash erosion - Chenjia Yuan; Junqiu Lin; Bing Wang; Daming Yang; Nufang Fang; Lingshan Ni; Zhihua Shi (CATENA, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Cytisine-like alkaloids from the seeds of Ormosia hosiei Hemsl. et Wils - Linjing Zhang; Lijun Zheng; Qin Wang; Zhenze Pana; Xiaoqin Zhang; Mingqing Huang; Huiyou Xu; Lin Ni (Natural Product Research, 2023)

Saltwater intrusion regulates the distribution and partitioning of heavy metals in water in a dynamic estuary, South China - Ling Zhang; Yunchao Wu; Zhixin Ni; Jinlong Li; Yuzheng Ren; Jizhen Lin; Xiaoping Huang (Marine Environmental Research, 2023)

High altitude Pliocene to Pleistocene vegetation and climate change of the Kunlun Pass Basin, NE Tibetan Plateau - Florian Schwarz; Ulrich Salzmann; Feng Cheng; Jian Ni; Junsheng Nie; Megan R. Patchett; Xiangzhong Li; Lin Li; John Woodward; Carmala Garzione (Global and Planetary Change, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

Colletotrichum species causing anthracnose disease on avocado fruit in Taiwan - Chao-Jung Wu; Miao-Chun Lin; Hui-Fang Ni (European Journal of Plant Pathology, 2023)

Eradicating the tumor “seeds”: nanomedicines-based therapies against cancer stem cells - Lin Li; Rui Ni; Dan Zheng; Lin Chen (DARU Journal of Pharmaceutical Sciences, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Effects of coal molecular structure and pore morphology on methane adsorption and accumulation mechanism - Jingshuo Zhang; Xiaoming Ni; Ying Han; Junfeng Lin (Frontiers of Earth Science, 2023)

Evaluation of toxicity of polystyrene microplastics under realistic exposure levels in human vascular endothelial EA.hy926 cells - Yi-Chun Chen; Ku-Fan Chen; Kun-Yi Andrew Lin; Han-Pang Su; Dong-Ni Wu; Chia-Hua Lin (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Spatiotemporal patterns of organic carbon burial over the last century in Lake Qinghai, the largest lake on the Tibetan Plateau - Xianqiang Meng; Xi Chen; Qi Lin; Yilan Liu; Zhenyu Ni; Weiwei Sun; Enlou Zhang (Science of The Total Environment, 2023)

Enhanced sulfolane-contaminated groundwater degradation and power generation by a mini tubular microbial fuel cell/electro-Fenton combined system - Shu-Hui Liu; Yen-Ni Tsai; Chiaying Chen; Chi-Wen Lin; Ting-Jun Zhu (Process Safety and Environmental Protection, 2023)

The effect of cellulose on the combustion characteristics of coal slime: TG-FTIR, principal component analysis, and 2D-COS - Zhanshi Ni; Zhihui Song; Haobo Bi; Chunlong Jiang; Hao Sun; Zhicong Qiu; Liqun He; Qizhao Lin (Fuel, 2023)

Marker-assisted breeding of rice lines special for rice noodle-making by pyramiding the Wxg2 and ALKGC genes - Bin Teng; Fengshun Song; Quan Gan; Cuixiang Lin; Dahu Ni (Euphytica, 2023)

Towards real-time detection of ships and wakes with lightweight deep learning model in Gaofen-3 SAR images - Kaiyang Ding; Junfeng Yang; Hui Lin; Zhao Wang; Deyi Wang; Xiaohao Wang; Kai Ni; Qian Zhou (Remote Sensing of Environment, 2023)

Origin traceability of bottled mineral water imported into China using chemical and stable isotope fingerprints - Hao Wu; Haiquan Chen; Bingqing Yi; Karyne M. Rogers; Xuehai Bian; Ni Lin; Xiuwen Zhou; Baohui Jin; Zhi Yan; Haichao Zhou (Journal of Hydrology, 2023)

Corrigendum to “Investigation of the co-pyrolysis of coal slime and coffee industry residue based on machine learning methods and TG-FTIR: Synergistic effect, kinetics and thermodynamic” [Fuel 305 (2021) 121527] - Zhanshi Ni; Haobo Bi; Chunlong Jiang; Chengxin Wang; Junjian Tian; Wenliang Zhou; Hao Sun; Qizhao Lin (Fuel, 2023)

Long term toxicities following developmental exposure to perfluorooctanoic acid: Roles of peroxisome proliferation activated receptor alpha - Hao Ni; Junhua Yuan; Jing Ji; Yajie Guo; Shuping Zhong; Yongfeng Lin; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2023)

Surface adsorption guided design of semicrystalline nickel-iron hydroxide for highly-sensitive glucose sensing - Minyuan Tan; Ming Ni; Xinyu Liu; Bo Qu; Xi Lin; Daochuan Jiang; Yupeng Yuan; Haiwei Du (Chemical Engineering Journal, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Mechanism of simultaneous lead and chromium removal from contaminated wastewater by a schwertmannite-like mineral - Mingyan Shi; Yali Zhang; Weibin Hong; Jiayu Liu; Huijie Zhu; Xu Liu; Yuxin Geng; Zhenyin Cai; Shaonan Lin; Chengzhi Ni (Environmental Science and Pollution Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Multi-stage melt impregnation and magma–seawater interaction in a slow-spreading oceanic lithosphere: constraints from cumulates in the Lagkorco ophiolite (central Tibet) - Wei-Qi Zhang; Chuan-Zhou Liu; Tong Liu; Chang Zhang; Zhen-Yu Zhang; Xiao-Ni Li; Zhen Zhang; Yin-Zheng Lin (Contributions to Mineralogy and Petrology, 2022)

Prohibitin Protein Expression During Spermatogenesis in the Large Yellow Croaker, Larimichthys crocea - Chenwen Lin; Xinming Gao; Jie Ni; Shengshuo Zhang; Cheng Liu; Shengyu Luo; Chen Du; Xuebin Zheng; Congcong Hou; Daojun Tang; Chundan Zhang; Junquan Zhu (Journal of Ocean University of China, 2022)

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Maintenance of Epstein-Barr virus latency through interaction of LMP2A with CXCR4 - Ni Qin; Yan Zhang; Lin Xu; Wen Liu; Bing Luo (Archives of Virology, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

The different effects of intramuscularly-injected lactate on white and brown adipose tissue in vivo - Yaqian Qu; Siyu Chen; Lei Zhou; Min Chen; Lin Li; Yihan Ni; Jingquan Sun (Molecular Biology Reports, 2022)

Construction and comprehensive analysis of a lncRNA–mRNA interactive network to reveal a potential lncRNA for hepatic encephalopathy development - Chihao Zhang; Wei Ni; Yiming Zhu; Jiayun Lin; Hongjie Li; Zhifeng Zhao; Ke Wang; Haizhong Huo; Meng Luo (Human Cell, 2022)

An Adequate Supply of Bis(ethylmaltolato)oxidovanadium(IV) Remarkably Reversed the Pathological Hallmarks of Alzheimer’s Disease in Triple-Transgenic Middle-Aged Mice - Zhijun He; Lin Zheng; Xu Zhao; Xiaoqian Li; Hua Xue; Qionghui Zhao; Bingyu Ren; Nan Li; Jiazuan Ni; Yan Zhang; Qiong Liu (Biological Trace Element Research, 2022)

Biochemical and structural characterization of the cyanophage‐encoded phosphate‐binding protein: implications for enhanced phosphate uptake of infected cyanobacteria - Fangxin Zhao; Xingqin Lin; Kun Cai; YongLiang Jiang; Tianchi Ni; Yue Chen; Jianrong Feng; Shangyu Dang; Cong‐Zhao Zhou; Qinglu Zeng (Environmental Microbiology, 2022)
Summary To acquire phosphorus, cyanobacteria use the typical bacterial ABC‐type phosphate transporter, which is composed of a periplasmic high‐affinity phosphate‐binding protein PstS and a channel formed by two transmembrane proteins PstC and PstA. A putative pstS gene was identified in the genomes of cyanophages that infect the unicellular marine cyanobacteria Prochlorococcus and Synechococcus . However, it has not been determined whether the cyanophage PstS protein is functional during infection to enhance the phosphate uptake rate of host cells. Here we showed that the cyanophage P‐SSM2 PstS protein was abundant in the infected Prochlorococcus NATL2A cells and the host phosphate uptake rate was enhanced after infection. This is consistent with our biochemical and structural analyses showing that the phage PstS protein is indeed a high‐affinity phosphate‐binding protein. We further modelled the complex structure of phage PstS with host PstCA and revealed three putative interfaces that may facilitate the formation of a chimeric ABC transporter. Our results provide insights into the molecular mechanism by which cyanophages enhance the phosphate uptake rate of cyanobacteria. Phosphate acquisition by infected bacteria can increase the phosphorus contents of released cellular debris and virus particles, which together constitute a significant proportion of the marine dissolved organic phosphorus pool.

Hydrodynamic Analysis of Tidal Current Turbine under Water-Sediment Conditions - Yanjing Gao; Hongwei Liu; Yonggang Lin; Yajing Gu; Yiming Ni (Journal of Marine Science and Engineering, 2022)
The rivers connecting oceans generally carry sediment due to water and soil losses in China. Additionally, the maximum sediment concentration is 300 g/L, which is much higher than that of other countries. It is unknown whether seawater with sand particles will affect the power of tidal current turbine blades. It is therefore necessary to study the capture power of tidal current turbines in the water-sediment environment. In this study, the blade was divided into a number of transversal airfoil elements based on the blade element theory. The CFD-DPM model was employed to study the lift and drag coefficients of airfoil under multiphase flow, and the fluid–particle interaction was considered. The accuracy of this presented model was assessed using the experimental data of a 120 kW tidal current turbine in a water-sediment environment. Good agreement between the predictions and experimental data was observed. The effect of particle properties on the lift coefficient and the drag coefficient of airfoil were investigated in detail. Furthermore, the 120 kW tidal current turbine power was calculated based on the Blade Element Momentum theory under different particle concentrations. The results show that small diameter particles can improve the tidal current turbine power and the large diameter particle can reduce the power.

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Correction to: Pharmacological stimulation of sigma-1 receptor promotes activation of astrocyte via ERK1/2 and GSK3β signaling pathway - Yun Wang; Hua-feng Jiang; Jing Ni; Lin Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Identification of methylation markers for diagnosis of autism spectrum disorder - Bei Zhang; Xiaoyuan Hu; Yuefei Li; Yongkang Ni; Lin Xue (Metabolic Brain Disease, 2022)

Isobaric Tags for Relative and Absolute Quantitation-Based Proteomics Analysis Provides a New Perspective Into Unsynchronized Growth in Kuruma Shrimp (Marsupenaeus japonicus) - Jichen Zhao; Minze Liao; Zexu Lin; Yiyi Huang; Yunqi Zhong; Luyao Liu; Guoliang Chen; Zuotao Ni; Chengbo Sun (Frontiers in Marine Science, 2021)
Unsynchronized growth is a common phenomenon in farmed crustaceans. The underlying molecular mechanism of unsynchronized growth of crustaceans is unclear. In this study, a comparative proteomic analysis focusing on growth differences was performed using kuruma shrimp Marsupenaeus japonicus , an economic crustacean species, as the model. The study analyzed kuruma shrimp at fast growth stage and steady growth stage from both fast growth group and slow growth group by an Isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomic analysis method. A total of 1,720 proteins, including 12,291 peptides, were identified. Fifty-two and 70 differentially expressed proteins (DEPs) were identified in the fast growth stage and steady growth stage, respectively. Interestingly, 10 DEPs, including 14-3-3-epsilon-like, GPI, GPD1, MHC-1a, and MHC-1b, were presented in both growth stages. In addition, all these 10 DEPs shared the same expression tendency at these two growth stages. The results indicated that these 10 DEPs are potential growth biomarkers of M. japonicus . Proteins associated with faster growth of M. japonicus may promote cell growth and inhibit cell apoptosis through the Hippo signaling pathway. The fast growth group of M. japonicus may also achieve growth superiority by activating multiple related metabolic pathways, including glycolysis, glycerophospholipid metabolism and Citrate cycle. The present study provides a new perspective to explore the molecular mechanism of unsynchronized growth in crustacean species.

210Po-210Pb Disequilibrium in the Western North Pacific Ocean: Particle Cycling and POC Export - Qiangqiang Zhong; Tao Yu; Hui Lin; Jing Lin; Jianda Ji; Jialin Ni; Jinzhou Du; Dekun Huang (Frontiers in Marine Science, 2021)
Estimating the particulate organic carbon (POC) export flux from the upper ocean is fundamental for understanding the efficiency of the biological carbon pump driven by sinking particles in the oceans. The downward POC flux from the surface ocean based on 210 Po- 210 Pb disequilibria in seawater samples from the western North Pacific Ocean (w-NPO) was measured in the early summer (May-June) of 2018. All the profiles showed a large 210 Po deficiency relative to 210 Pb in the euphotic zone (0–150 m), while this 210 Po deficiency vanished below ∼500 m (with 210 Po/ 210 Pb ∼1 or > 1). A one-dimensional steady-state irreversible scavenging model was used to quantify the scavenging and removal fluxes of 210 Po and 210 Pb in the euphotic zone of the w-NPO. In the upper ocean (0–150 m), dissolved 210 Po (D-Po) was scavenged into particles with a residence time of 0.6–5.5 year, and the 210 Po export flux out of the euphotic zone was estimated as (0.33–3.49) × 10 4 dpm/m 2 /year, resulting in a wide range of particulate 210 Po (P-Po) residence times (83–921 days). However, in the deep ocean (150–1,000 m), 210 Po was transferred from the particulate phase to the dissolved phase. Using an integrated POC inventory and the P-Po residence times (Eppley model) in the w-NPO euphotic zone, the POC export fluxes (mmol C/m 2 /d) varied from 0.6 ± 0.2 to 8.8 ± 0.4. In comparison, applying the POC/ 210 Po ratio of all (>0.45 μm) particles to 210 Po export flux (Buesseler model), the obtained POC export fluxes (mmol C/m 2 /d) ranged from 0.7 ± 0.1 to 8.6 ± 0.8. Both Buesseler and Eppley methods showed enhanced POC export fluxes at stations near the continental shelf (i.e., Luzon Strait and the Oyashio-Kuroshio mixing region). The Eppley model-based 210 Po-derived POC fluxes agreed well with the Buesseler model-based fluxes, indicating that both models are suitable for assessing POC fluxes in the w-NPO. The POC export efficiency was < 15%, suggesting a moderate biological carbon pump efficiency in the w-NPO. These low export efficiencies may be associated with the dominance of smaller particles and the processes of degradation and subsequent remineralization of these small particles in the euphotic zone of oligotrophic regions in the w-NPO.

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Bacterial communities in cascade reservoirs along a large river - Qiuwen Chen; Yuchen Chen; Jun Yang; Stephen C. Maberly; Jianyun Zhang; Jinren Ni; Gangsheng Wang; Daniele Tonina; Lin Xiao; Honghai Ma (Limnology and Oceanography, 2021)
Dam construction is widespread, changing the hydrological and biogeochemical conditions and thereby the bacterial communities in the rivers of the earth. To date, knowledge is lacking about bacterial communities in cascade reservoirs. Here, we investigated the bacterial communities and potential functions of nine cascade hydropower reservoirs in 1290 km of the upper Mekong River (Lancang River in China). Along the reservoir cascade, the water temperature, rather than the presence of dams, was the main cause for the geographical patterns of bacterial community composition. Within a reservoir, significant spatial differences in sediment bacterial communities were observed between the tail, middle, and head of a reservoir. The differences in sediment properties resulted by flow velocity‐sieved sedimentation from the tail to head of a reservoir caused the spatial variation in sediment bacteria communities, forming potential hotspots for biogeochemical cycling in the middle of the reservoir. In contrast, unlike in deep lakes and deep single reservoirs, the bacterioplankton community composition had no distinctly layered features in the deep cascade reservoirs, because density‐induced underwater currents and convection resulting from hydropower production reduced the vertical hydro‐environmental gradients. This study provides a novel perspective on the processes affecting the distribution and function of bacterial communities in river‐reservoir cascades, and is a first step toward forecasting the consequences of microbially mediated biogeochemical cycling in existing and future reservoirs worldwide.

Linking circular intronic RNA degradation and function in transcription by RNase H1 - Xiang Li; Jia-Lin Zhang; Yun-Ni Lei; Xiao-Qi Liu; Wei Xue; Yang Zhang; Fan Nan; Xiang Gao; Jun Zhang; Jia Wei; Li Yang; Ling-Ling Chen (Science China Life Sciences, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Hositisines A and B, new alkaloids from the stems of Ormosia hosiei Hemsl. et Wils - Lin Ni; Jingxin Chen; Xiaoqin Zhang; Meiting Wu; Linjing Zhang; Zujian Wu; Mingqing Huang; Huiyou Xu (Natural Product Research, 2021)

Eco-efficiency evaluation model: a case study of the Yangtze River Economic Belt - Xu Xu; Lin-Chao Pan; Qing-He Ni; Qian-Qian Yuan (Environmental Monitoring and Assessment, 2021)

Anthracnose disease of Amomum villosum caused by Colletotrichum fructicola in China - Lisha Song; Wei Lin; Ni Jiang; Zhanjiang Zhang; Guiyu Tan; Shugen Wei (Journal of General Plant Pathology, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Genome-Wide Identification, Characterization of bHLH Transcription Factors in Mango - Haron Salih; Lin Tan; Nwe Ni Win Htet (Tropical Plant Biology, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Boys with autism spectrum disorder have distinct cortical folding patterns underpinning impaired self-regulation: a surface-based morphometry study - Hsing-Chang Ni; Hsiang-Yuan Lin; Yu-Chieh Chen; Wen-Yih Isaac Tseng; Susan Shur-Fen Gau (Brain Imaging and Behavior, 2020)

MicroRNA-107 Ameliorates Damage in a Cell Model of Alzheimer’s Disease by Mediating the FGF7/FGFR2/PI3K/Akt Pathway - Wei Chen; Lin Wu; Yueqiang Hu; Lingfei Jiang; Ni Liang; Jing Chen; Hongling Qin; Nong Tang (Journal of Molecular Neuroscience, 2020)

Preparation and uranium (VI) biosorption for tri-amidoxime modified marine fungus material - Jingwen Han; Lin Hu; Leqing He; Kang Ji; Yaqing Liu; Can Chen; Xiaomei Luo; Ni Tan (Environmental Science and Pollution Research, 2020)

Phase-field modeling of hydraulic fracture network propagation in poroelastic rocks - Lin Ni; Xue Zhang; Liangchao Zou; Jinsong Huang (Computational Geosciences, 2020)
Modeling of hydraulic fracturing processes is of great importance in computational geosciences. In this paper, a phase-field model is developed and applied for investigating the hydraulic fracturing propagation in saturated poroelastic rocks with pre-existing fractures. The phase-field model replaces discrete, discontinuous fractures by continuous diffused damage field, and thus is capable of simulating complex cracking phenomena such as crack branching and coalescence. Specifically, hydraulic fracturing propagation in a rock sample of a single pre-existing natural fracture or natural fracture networks is simulated using the proposed model. It is shown that distance between fractures plays a significant role in the determination of propagation direction of hydraulic fracture. While the rock permeability has a limited influence on the final crack topology induced by hydraulic fracturing, it considerably impacts the distribution of the fluid pressure in rocks. The propagation of hydraulic fractures driven by the injected fluid increases the connectivity of the natural fracture networks, which consequently enhances the effective permeability of the rocks.

Chemical constituents from the bark of bauhinia purpurea and their NO inhibitory activities - Lin Ni; Wei Huang; Yan Shi; Heshan Wang; Yatie Qiu; Huiyou Xu (Natural Product Research, 2020)

Electrolytic enrichment method for tritium determination in the Arctic Ocean using liquid scintillation counter - Feng Lin; Tao Yu; Wen Yu; Jialin Ni; Li Lin (Acta Oceanologica Sinica, 2020)

The impact of secondary inorganic aerosol emissions change on surface air temperature in the Northern Hemisphere - Chunjiang Zhou; Peng Liu; Gang Huang; Jintai Lin; Kaiming Hu; Lulu Chen; Jingxu Wang; Sixuan Li; Su Wang; Ruijing Ni (Theoretical and Applied Climatology, 2020)

Herpud1 deficiency could reduce amyloid-β40 expression and thereby suppress homocysteine-induced atherosclerosis by blocking the JNK/AP1 pathway - Feidan Gao; Jie Zhang; Tingjuan Ni; Na Lin; Hui Lin; Hangqi Luo; Hangyuan Guo; Jufang Chi (Journal of Physiology and Biochemistry, 2020)

Hydrogen sulfide is a crucial element of the antioxidant defense system in Glycine max–Sinorhizobium fredii symbiotic root nodules - Hang Zou; Ni-Na Zhang; Xue-Yuan Lin; Wei-Qin Zhang; Jian-Hua Zhang; Juan Chen; Ge-Hong Wei (Plant and Soil, 2020)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Probiotic Clostridium butyricum Improves the Growth Performance, Immune Function, and Gut Microbiota of Weaning Rex Rabbits - Lei Liu; Dong Zeng; Mingyue Yang; Bin Wen; Jing Lai; Yi Zhou; Hao Sun; Lvcheng Xiong; Jie Wang; Yicen Lin; Kangcheng Pan; Bo Jing; et al. (Probiotics and Antimicrobial Proteins, 2019)

A full-scale study of external circulation sludge bed (ECSB) system for anaerobic wastewater treatment in a whiskey distillery - Yu-Chung Lin; Chen-Hua Ni; Chin-Yi Wu; Justin Chun-Te Lin (Environmental Science and Pollution Research, 2019)

Phytotoxicity and oxidative effects of typical quaternary ammonium compounds on wheat (Triticum aestivum L.) seedlings - Yafei Li; Can Zhou; Shizhong Wang; Qingqi Lin; Zhuobiao Ni; Hao Qiu; Jean Louis Morel; Rongliang Qiu (Environmental Science and Pollution Research, 2019)

Tsunami Hazard and Built Environment Damage Observations from Palu City after the September 28 2018 Sulawesi Earthquake and Tsunami - Ryan Paulik; Aditya Gusman; James H. Williams; Gumbert Maylda Pratama; Sheng-lin Lin; Alamsyah Prawirabhakti; Ketut Sulendra; Muhammad Yasser Zachari; Zabin Ellyni Dwi Fortuna; Novita Barrang Pare Layuk; Ni Wayan Ika Suwarni (Pure and Applied Geophysics, 2019)

Impaired autophagy mediates hyperhomocysteinemia-induced HA-VSMC phenotypic switching - Tingjuan Ni; Feidan Gao; Jie Zhang; Hui Lin; Hangqi Luo; Jufang Chi; Hangyuan Guo (Journal of Molecular Histology, 2019)

Pharmacological stimulation of sigma-1 receptor promotes activation of astrocyte via ERK1/2 and GSK3β signaling pathway - Yun Wang; Hua-feng Jiang; Jing Ni; Lin Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Development and validation of nomogram estimating post-surgery hospital stay of lung cancer patients: relevance for predictive, preventive, and personalized healthcare strategies - Xiang-Lin Hu; Song-Tao Xu; Xiao-Cen Wang; Jin-Long Luo; Dong-Ni Hou; Xiao-Min Zhang; Chen Bao; Dong Yang; Yuan-Lin Song; Chun-Xue Bai (EPMA Journal, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Imaging study of pseudo-CT images of superposed ultrasound deformation fields acquired in radiotherapy based on step-by-step local registration - Hongfei Sun; Tao Lin; Kai Xie; Liugang Gao; Jianfeng Sui; Xinye Ni (Medical & Biological Engineering & Computing, 2019)

Numerical assessments of recharge-dominated groundwater flow and transport in the nearshore reclamation area in western Taiwan - Chuen-Fa Ni; Wei-Ci Li; Shaohua Marko Hsu; I-Hsien Lee; Chi-Ping Lin (Environmental Monitoring and Assessment, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Influence of soil variability on single and competitive interaction of ammonium and potassium: experimental study on seven different soils - Poly Buragohain; S. Sreedeep; Peng Lin; Junjun Ni; Ankit Garg (Journal of Soils and Sediments, 2019)

TGF-β1 Restores Hippocampal Synaptic Plasticity and Memory in Alzheimer Model via the PI3K/Akt/Wnt/β-Catenin Signaling Pathway - Yueqiang Hu; Wei Chen; Lin Wu; Lingfei Jiang; Ni Liang; Lulu Tan; Minghui Liang; Nong Tang (Journal of Molecular Neuroscience, 2019)

Investigation on pseudorabies prevalence in Chinese swine breeding farms in 2013–2016 - Yingyi Liu; Shuo Zhang; Qi Xu; Jiajun Wu; Xinyan Zhai; Shuo Li; Jing Wang; Jianqiang Ni; Lin Yuan; Xiaohui Song; Bolin Zhao; Zhi Zhou; et al. (Tropical Animal Health and Production, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Targeted next-generation sequencing improves diagnosis of hereditary spastic paraplegia in Chinese patients - Cong Lu; Li-Xi Li; Hai-Lin Dong; Qiao Wei; Zhi-Jun Liu; Wang Ni; Aaron D. Gitler; Zhi-Ying Wu (Journal of Molecular Medicine, 2018)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

Identification of inhibitors synergizing gemcitabine sensitivity in the squamous subtype of pancreatic ductal adenocarcinoma (PDAC) - Jia Lin Er; Pei Ni Goh; Chen Yuan Lee; Ying Jie Tan; Ling-Wei Hii; Chun Wai Mai; Felicia Fei-Lei Chung; Chee-Onn Leong (Apoptosis, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Transcriptome profile analysis reveals cardiotoxicity of maduramicin in primary chicken myocardial cells - Xiuge Gao; Lin Peng; Xiangchun Ruan; Xin Chen; Hui Ji; Junxiao Ma; Han Ni; Shanxiang Jiang; Dawei Guo (Archives of Toxicology, 2018)

Current advances in the development of natural meniscus scaffolds: innovative approaches to decellularization and recellularization - Yunbin Chen; Jiaxin Chen; Zeng Zhang; Kangliang Lou; Qi Zhang; Shengyu Wang; Jinhu Ni; Wenyue Liu; Shunwu Fan; Xianfeng Lin (Cell and Tissue Research, 2017)

Stress distribution characteristic analysis and control of coal and gas outburst disaster in a pressure-relief boundary area in protective layer mining - Zhen Liu; He Yang; Weimin Cheng; Lin Xin; Guanhua Ni (Arabian Journal of Geosciences, 2017)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Distance-dependent varieties of microbial community structure and metabolic functions in the rhizosphere of Sedum alfredii Hance during phytoextraction of a cadmium-contaminated soil - Wenhao Yang; Taoxiang Zhang; Sen Lin; Wuzhong Ni (Environmental Science and Pollution Research, 2017)

Association analysis between HFM1 variations and idiopathic azoospermia or severe oligozoospermia in Chinese Men - Wenxiang Zhang; Xiaomin Song; Feng Ni; Jinbao Cheng; Bai-Lin Wu; Hong Jiang (Science China Life Sciences, 2017)

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Repair process and enzymatic activity associated with induction of shell regeneration in the invasive species Pomacea canaliculata - Song Yang; Lin-kang Ni; Liu-lan Zhao; Jin-wei Yang; Qiao Liu; Jia-en Zhang; Zhi He; Shuang Peng (Molluscan Research, 2016)

Environmental and cortisol-mediated control of Ca2+ uptake in tilapia (Oreochromis mossambicus) - Chia-Hao Lin; Wei-Chun Kuan; Bo-Kai Liao; Ang-Ni Deng; Deng-Yu Tseng; Pung-Pung Hwang (Journal of Comparative Physiology B, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Phosphorus-controlled trace element distribution in zircon revealed by NanoSIMS - Wei Yang; Yangting Lin; Jialong Hao; Jianchao Zhang; Sen Hu; Huaiwei Ni (Contributions to Mineralogy and Petrology, 2016)

Soil organic carbon pool along different altitudinal level in the Sygera Mountains, Tibetan Plateau - He-ping Ma; Xiao-lin Yang; Qi-qiang Guo; Xin-jun Zhang; Chen-ni Zhou (Journal of Mountain Science, 2016)

A new flavonol glycoside from the florets of Carthamus tinctorius L. - Xue Xie; Jianming Zhou; Lin Sun; Hongda Zhang; Yiwu Zhao; Yaling Song; Xuejing Wang; Fuyong Ni; Wenzhe Huang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2016)

Geomorphologic analysis and physico-dynamic characteristics of Zhatai-Gully debris flows in SW China - Xi-lin Liu; Chuan Tang; Hua-yong Ni; Yuan Zhao (Journal of Mountain Science, 2016)

The RNA-binding protein Sam68 regulates tumor cell viability and hepatic carcinogenesis by inhibiting the transcriptional activity of FOXOs - Tingting Zhang; Chunhua Wan; Weidong Shi; Jian Xu; Hui Fan; Shusen Zhang; Zhipeng Lin; Runzhou Ni; Xiubing Zhang (Journal of Molecular Histology, 2015)

Impact of the geological structure on pulsating hydraulic fracturing - Ni Guanhua; Lin Baiquan; Zhai Cheng (Arabian Journal of Geosciences, 2015)

Bergapten promotes bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo - Ji-jie Xiao; Wen-ji Zhao; Xin-tao Zhang; Wen-long Zhao; Xiao-xia Wang; Shu-hui Yin; Fang Jiang; Yin-xia Zhao; Fang-ni Chen; Shao-lin Li (Molecular and Cellular Biochemistry, 2015)

The determination of sex type of the cultured murine cell with quantitative PCR technique - Qian Wan; Liang Ni; Lintao Wu; Lin Zhang; Mianxue Liu; Xiaohui Jiang (Human Cell, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Organochlorine pesticides and their metabolites in human breast milk from Shanghai, China - Dasheng Lu; Dongli Wang; Rong Ni; Yuanjie Lin; Chao Feng; Qian Xu; Xiaodong Jia; Guoquan Wang; Zhijun Zhou (Environmental Science and Pollution Research, 2015)

Fast-growing and poorly shade-tolerant invasive species may exhibit higher physiological but not morphological plasticity compared with non-invasive species - Yu-Ping Hou; Shao-Lin Peng; Zhen-Guang Lin; Qiao-Qiao Huang; Guang-Yan Ni; Na Zhao (Biological Invasions, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

Denbinobin upregulates miR-146a expression and attenuates IL-1β-induced upregulation of ICAM-1 and VCAM-1 expressions in osteoarthritis fibroblast-like synoviocytes - Chia-Ron Yang; Kao-Shang Shih; Jing-Ping Liou; Yi-Wen Wu; I-Ni Hsieh; Hsueh-Yun Lee; Tzu-Cheng Lin; Jyh-Horng Wang (Journal of Molecular Medicine, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Classification and identification of metal-accumulating plant species by cluster analysis - Wenhao Yang; He Li; Taoxiang Zhang; Lin Sen; Wuzhong Ni (Environmental Science and Pollution Research, 2014)

Petrographic and geochemical characteristics of the Paleogene sedimentary rocks from the North Jiangsu Basin, Eastern China: implications for provenance and tectonic setting - Ni Zhang; Chun-Ming Lin; Xia Zhang (Mineralogy and Petrology, 2014)

Characteristics and sedimentary processes of lamina-controlled sand-particle imbricate structure in deposits on Lingshan Island, Qingdao, China - ZhuFu Shao; JianHua Zhong; Yong Li; Cui Mao; ShengXin Liu; LiangTian Ni; Yuan Tian; XinYing Cui; YunTian Liu; XiaoNan Wang; WeiHua Li; GangShan Lin (Science China Earth Sciences, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Expression of HAb18G in non-small lung cancer and characterization of activation, migration, proliferation, and apoptosis in A549 cells following siRNA-induced downregulation of HAb18G - Xiaoyan Xu; Shuguang Liu; Bin Lei; WenXia Li; Ni Lin; Wenjie Sheng; Aili Huang; Hong Shen (Molecular and Cellular Biochemistry, 2013)

APRIL depletion induces cell cycle arrest and apoptosis through blocking TGF-β1/ERK signaling pathway in human colorectal cancer cells - Feng Wang; Lin Chen; Hongbin Ni; Guihua Wang; Weifeng Ding; Hui Cong; Shaoqing Ju; Shumei Yang; Huimin Wang (Molecular and Cellular Biochemistry, 2013)

Vascular endothelial growth factor (VEGF) gene polymorphisms and risk of head and neck cancer: a meta-analysis involving 2,444 individuals - Wei-Dong Leng; Mei-Ni He; Qi-Lin Chen; Heng Gong; Li Zhang; Xian-Tao Zeng (Molecular Biology Reports, 2013)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Longitudinal patterns of spring-intermonsoon phytoplankton biomass, species compositions and size structure in the Bay of Bengal - Gang Li; Zhixin Ke; Qiang Lin; Guangyan Ni; Pingping Shen; Huaxue Liu; Jianqiang Yin; Kaizhi Li; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)

When interspecific prezygotic barriers break down: hybridization between two Potamogeton species (P. wrightii and P. perfoliatus) and comparison of the artificial and natural hybrids - Xiao-Lin Zhang; Xiao-Xia Li; Le-Yi Ni; You-Hao Guo (Plant Systematics and Evolution, 2011)

Tectonics and mechanisms of uplift in the central uplift belt of the Huimin depression - Jinlong Ni; Ying Guo; Zhimin Wang; Junlai Liu; Yuxiang Lin; Yue Li (Journal of Earth Science, 2011)

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China - Yu-Ping Hou; Shao-Lin Peng; Bao-Ming Chen; Guang-Yan Ni (Biological Invasions, 2011)

Implication of life history strategies for prenatal investment in cetaceans - Shiang‐Lin Huang; Lien‐Siang Chou; Nien‐Tsu Shih; I‐Hsun Ni (Marine Mammal Science, 2011)
Prenatal investment directly determines the size at birth and fetus growth rate, which affects neonatal survival and growth and potentially affects maternal fitness. This study explored the associated prenatal life history traits of cetaceans. Using multivariate analysis and ANCOVA, baleen whales and toothed cetaceans had distinct energy patterns, with two exceptions including beaked whales and eusocial cetaceans. Baleen whales are characterized by fast prenatal growth, which suggests high prenatal energetics, and utilize the capital breeder tactic. Toothed cetaceans, except for beaked whales, utilize income breeder energetics, which yields relatively slow prenatal growth. However, eusocial cetaceans have especially slow prenatal growth, suggesting very low prenatal energetic effort with social compensation. Although beaked whales are behaviorally income breeders, both discriminant analysis and ANCOVA showed that they are energetically similar to baleen whales, utilizing capital energetics. ANCOVA further revealed that beaked whales have comparatively large calf size, suggesting high prenatal investment. Because all cetaceans wean their calves at comparable size, high prenatal investment may further suggest reduced cost of lactation, which may be behaviorally and energetically adaptive to their specific deep‐dive‐feeding niche.

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Acroptilon repens, an Asian invader, has stronger competitive effects on species from America than species from its native range - Guang-Yan Ni; Urs Schaffner; Shao-Lin Peng; Ragan M. Callaway (Biological Invasions, 2010)

An alkali-tolerant xylanase produced by the newly isolated alkaliphilic Bacillus pumilus from paper mill effluent - Jing Wang; Wei-wei Zhang; Jin-ni Liu; Yao-ling Cao; Xiao-ting Bai; Yue-sheng Gong; Pei-lin Cen; Ming-ming Yang (Molecular Biology Reports, 2010)

Modeling air gun signatures in marine seismic exploration considering multiple physical factors - Guo-Fa Li; Ming-Qiang Cao; Hao-Lin Chen; Cheng-Zhou Ni (Applied Geophysics, 2010)

Comparable length at weaning in cetaceans - Shiang‐lin Huang; Lien‐Siang Chou; I‐Hsun Ni (Marine Mammal Science, 2009)
Weaning represents the transition of mammalian life from maternal dependence to independence in both energetics and behavior. The length at weaning ( Lw ) is determined by the maternal investment during gestation and lactation. It affects calf survival and impacts on the long‐term persistence of species, but the measurement is not readily obtainable for many cetaceans. A general linear model and residual correlation were used to explore the correlations between the published Lw and five other life history traits of cetaceans, including female asymptotic length ( Lx ), length at birth ( Lb ), lactation period ( LP ), gestation period ( GP ), and calving interval ( CI ). Lx was a significant confounding parameter on the other five traits. By eliminating the confounding Lx , ANCOVA revealed that baleen whales (Mysticeti) and toothed cetaceans (Odontoceti) had comparable Lw. By residual correlation, which factors the confounding Lx , Lw was significantly correlated with Lb but not with GP , LP , and CI. After Lb was further eliminated, convergent Lw in cetaceans could still be observed. Therefore, we proposed a generic expression Lw = 1.239 Lx 0.877 , which allows us to further estimate Lw of undocumented cetacean species.

Effects of the invasive plant Mikania micrantha H.B.K. on soil nitrogen availability through allelopathy in South China - Bao-Ming Chen; Shao-Lin Peng; Guang-Yan Ni (Biological Invasions, 2009)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

Lignans and anthraquinones from the fruits of Morinda citrifolia - Chwan Fwu Lin; Ching Li Ni; Yu Ling Huang; Shuenn Jyi Sheu; Chien Chih Chen (Natural Product Research, 2007)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Genetic diversity of the endangered Chinese endemic herb Primulina tabacum (Gesneriaceae) revealed by amplified fragment length polymorphism (AFLP) - Xiaowei Ni; Yelin Huang; Lin Wu; Renchao Zhou; Shulin Deng; Darong Wu; Bosun Wang; Guohua Su; Tian Tang; Suhua Shi (Genetica, 2006)

Isolation and characterization of 18 genes encoding α- and β-expansins in wheat (Triticum aestivum L.) - Zhan Lin; Zhongfu Ni; Yi Zhang; Yingyin Yao; Haiyan Wu; Qixin Sun (Molecular Genetics and Genomics, 2005)

Four-dimensional variational data assimilation experiments for a heavy rain case during the 2002 IOP in China - Zhang Lin; Ni Yunqi (Advances in Atmospheric Sciences, 2005)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

The maintenance of the blocking over the ural mountains during the second Meiyu period in the summer of 1998 - Li Shuanglin; Ji Liren; Lin Wantao; Ni Yunqi (Advances in Atmospheric Sciences, 2001)

Inhibitory effect of phycocyanin from Spirulina platensis on the growth of human leukemia K562 cells - Yufeng Liu; Lizhi Xu; Ni Cheng; Lijun Lin; Chengwu Zhang (Journal of Applied Phycology, 2000)

Numerical study for potential predictability of short— term anomalous climate change caused by El nino - Ni Yunqi; Lin Wuyin; Wang Wanqiu; Yuan Chongguang; Zhang Qin (Advances in Atmospheric Sciences, 1993)

Seasonal characteristics and internnual variability of monthly scale low-frequency oscillation in a low-order global spectral model - Ni Yunqi; Zhang Qin; Lin Wuyin (Advances in Atmospheric Sciences, 1991)

Numerical study for characteristic change of Asian summer monsoon circulation and its influence mechanism during the El Nino period - Yunqi Ni; Yuanbi Lin (Advances in Atmospheric Sciences, 1990)